Laminate
Patent Information
- Application Number
- JP2021518341
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-09
- Filing Date
- 2020-04-23
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-04-23
AI Technical Summary
【0013】 本発明の積層体は、ガラス基板又はシリコン基板からポリイミドフィルムを、機械的に剥離する場合であっても、容易かつ安定的に剥離することができる。したがって、本発明の積層体は、樹脂基板を備えるフレキシブル電子デバイスの製造プロセスの簡便化やその歩留り向上等に寄与し得る。 また、ポリイミドフィルムは無色透明性及び光学的等方性に優れる。したがって、ガラス基板又はシリコン基板から剥離されたフィルムは、フレキシブル電子デバイス用の樹脂基板として好適である。
Smart Images

Figure 0007632280000001 
Figure 0007632280000002 
Figure 0007632280000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, and more particularly to a laminate in which a polyimide film is adhered to a glass substrate or a silicon substrate, and a metal film or an oxide semiconductor film is further laminated on the polyimide film. [Background technology]
[0002] Various applications of polyimide resins are being considered in the fields of electric and electronic components, etc. For example, it is desirable to replace glass substrates used in image display devices such as liquid crystal displays and OLED displays with plastic substrates in order to make the devices lighter and more flexible, and research is being conducted on polyimide films suitable for such plastic substrates. In an image display device, when light emitted from a display element is emitted through a plastic substrate, the plastic substrate is required to be colorless and transparent. Furthermore, when light passes through a retardation film or a polarizing plate (for example, a liquid crystal display, a touch panel, etc.), in addition to colorless transparency, the substrate is also required to have high optical isotropy (i.e., low Rth).
[0003] When a polyimide film is used as a substrate, the desired electronic circuit is formed on the polyimide film through various processes such as a sputtering process and an etching process for forming an oxide semiconductor film such as an indium tin oxide (ITO) film depending on the application. When forming the desired electronic circuit on the polyimide film, the polyimide film is adhered to a hard support such as a glass plate in order to ensure the flatness of the polyimide film. At this time, if the polyimide film is not adhered to the support, a problem occurs in the process. In addition, after these processes, a process of peeling the polyimide film from the support is required. This peeling process is performed after cooling the molded body on the substrate to room temperature to about 50°C.
[0004] Known methods for adhering a polyimide film to a support include adding an adhesive to the polyimide itself, and interposing a layer called a release layer between the polyimide film and the support to ensure adhesion during processing.
[0005] As a method for peeling off a polyimide film from a support, for example, the following method is known. (1) A method in which a structure containing a polyimide resin / support is obtained, and then a laser is irradiated from the support side to ablate the polyimide resin interface, thereby peeling off the polyimide resin (see, for example, Patent Document 1). The types of lasers used include solid (YAG) lasers and gas (UV excimer) lasers, and a spectrum of 308 nm or the like is used. (2) A method in which a release layer is formed on the support before the resin composition is applied to the support, and then a structure including a polyimide resin film / release layer / support is obtained, and the polyimide resin film is mechanically peeled off (see, for example, Patent Document 2). Examples of the release layer include a method using Parylene (registered trademark, manufactured by Nippon Parylene LLC) or tungsten oxide, and a method using a vegetable oil-based, silicone-based, fluorine-based, or alkyd-based release agent. In addition, the laser irradiation described in (1) above may also be used in combination.
[0006] Patent Document 3 discloses a method for fixing a resin substrate to a support substrate via an adhesive layer, forming an electronic element on the resin substrate, and peeling an electronic device including the electronic element and the resin substrate from the support substrate, in which an adhesive layer containing a material whose adhesive strength with the support substrate decreases upon contact with moisture is used as a main component.
[0007] On the other hand, Patent Document 4 discloses that the water content in a resin composition containing a polyimide precursor and an organic solvent is reduced from the viewpoint of imidization of polyamic acid and storage stability of the resin composition. That is, it is believed that the acid anhydride groups of some acid dianhydride monomers are hydrolyzed to carboxyl groups due to the influence of moisture, and remain in a low molecular weight state without being made into a high molecular weight. It is also believed that moisture is involved in the decomposition and recombination of the polyimide precursor, which affects the viscosity stability of the resin composition during storage. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 2007-512568 [Patent Document 2] JP 2010-067957 A [Patent Document 3] JP 2016-021384 A [Patent Document 4] JP 2018-145440 A Summary of the Invention [Problem to be solved by the invention]
[0009] The method (1) above has the problem that the resin substrate formed on the base body may be damaged during laser irradiation, and also has the problem of having to introduce an expensive laser irradiation device, which is costly. In the method (2) above, a laser irradiation device is not necessary, but depending on the type of polyimide, the release layer may not fully exhibit its function. In the method of Patent Document 3, when forming an electronic element, it was necessary to form a sealing layer to seal the exposed portion of the adhesive layer in order to prevent the adhesive layer from coming into contact with moisture so as not to reduce the adhesive strength. On the other hand, when peeling off the electronic device after forming the electronic element, it was necessary to remove the sealing layer before peeling off in order to bring the adhesive layer into contact with moisture. Therefore, the method of Patent Document 3 was a complicated process overall. Furthermore, it was necessary to place the device in a high humidity environment of 90% or more in order to bring the device into contact with moisture, and there was a problem that it was difficult to control the moisture content and ensure stable peelability.
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a laminate comprising a polyimide film adhered to a glass substrate or a silicon substrate, and a metal film or an oxide semiconductor film further laminated on the polyimide film, wherein the polyimide film is excellent in colorless transparency and optical isotropy, and the polyimide film can be easily and stably peeled off from the glass substrate or the silicon substrate. [Means for solving the problem]
[0011] The present inventors have surprisingly found that the above-mentioned problems can be solved by intentionally incorporating an optimum amount of moisture in the film, whereas the content of moisture was conventionally required to be reduced. The present invention was completed based on this finding.
[0012] That is, the present invention relates to the following. <1> A laminate comprising a polyimide film adhered to a glass substrate or a silicon substrate, and a metal film or an oxide semiconductor film further laminated on the polyimide film, wherein the metal film or the oxide semiconductor film has a thickness of 1 to 400 nm, and the polyimide film has a moisture content of 1,000 to 35,000 ppm by mass. <2> The polyimide film has a peel strength of 20 gf / cm or less from a glass substrate or a silicon substrate. <1> The laminate according to claim 1. <3> The polyimide film has a thickness of 3 to 20 μm. <1> or <2> The laminate according to claim 1. <4> The oxide semiconductor film is at least one selected from the group consisting of indium tin oxide, amorphous silicon, indium gallium zinc oxide, and low-temperature polysilicon. <1> ~ <3> 13. The laminate according to claim 12 . <5> the above <1> ~ <4> 2. A conductive film obtained by peeling off the glass substrate or silicon substrate from the laminate described in any one of 1 to 11. <6> A step of laminating a polyimide film on a glass substrate or a silicon substrate; A step of adjusting the moisture content of the polyimide film to 1,000 to 35,000 ppm by mass; A step of laminating a metal film or an oxide semiconductor film having a thickness of 1 to 400 nm on a polyimide film; and A process of peeling off and removing the glass substrate or silicon substrate A method for producing a conductive film comprising the steps of: <7> The step of adjusting the moisture content of the polyimide film is a step of holding the film in a temperature and humidity environment of 10 to 40° C. and 40 to 80% RH for 20 hours or more. <6> 2. A method for producing a conductive film according to claim 1 . <8> The step of laminating a metal film or an oxide semiconductor film on the polyimide film is performed by a physical vapor deposition method or a chemical vapor deposition method. <6> or <7> 2. A method for producing a conductive film according to claim 1 . Effect of the Invention
[0013] The laminate of the present invention allows the polyimide film to be easily and stably peeled off from the glass substrate or silicon substrate even when the polyimide film is mechanically peeled off from the glass substrate or silicon substrate, and therefore the laminate of the present invention can contribute to simplifying the manufacturing process of flexible electronic devices having resin substrates and improving the yield thereof. Furthermore, polyimide films are excellent in colorless transparency and optical isotropy, and therefore, when peeled off from a glass substrate or a silicon substrate, the film is suitable as a resin substrate for a flexible electronic device.
Embodiments for Carrying Out the Invention
[0014] Hereinafter, an embodiment of the present invention will be described. The content of the present invention is not limited to the embodiments described below. In this specification, the term "A to B" regarding the description of numerical values means "A or more and B or less" (when A < B) or "A or less and B or more" (when A > B). Also, in the present invention, a combination of preferred embodiments is a more preferred embodiment.
[0015] The laminate of the present invention is a laminate in which a polyimide film is adhered to a glass substrate or a silicon substrate, and a metal film or an oxide semiconductor film is further laminated on the polyimide film, wherein the thickness of the metal film or the oxide semiconductor film is 1 to 400 nm, and the water content of the polyimide film is 1,000 to 35,000 mass ppm.
[0016] (Glass substrate or silicon substrate) The glass substrate or the silicon substrate is not particularly limited, and it suffices if it has a strength sufficient to support the polyimide film when manufacturing an electronic device (conductive film) using the polyimide film as a substrate. The type of glass is also not particularly limited, and non-alkali glass (borosilicate glass), alkali glass, soda glass, non-fluorescent glass, phosphate-based glass, boric acid-based glass, quartz, etc. can be used. In order to improve the adhesion to the polyimide film, it is preferable that the flatness of the upper surface of the glass substrate or the silicon substrate is high. Specifically, the surface roughness Rmax is preferably 10 μm or less, and more preferably 1 μm or less.
[0017] (Polyimide film) In the laminate of the present invention, a polyimide film is adhered to a glass substrate or a silicon substrate. The polyimide film is preferably adhered directly to the glass substrate or the silicon substrate, and it is preferable that no adhesive layer or the like is interposed between the glass substrate or the silicon substrate and the polyimide film.
[0018] The water content of the polyimide film in the present invention is 1,000 to 35,000 ppm by mass, preferably 3,000 to 30,000 ppm by mass, and more preferably 5,000 to 25,000 ppm by mass. When the water content of the polyimide film is within this range, the polyimide film can be stably peeled off from a glass substrate or a silicon substrate after the production of an electronic device.
[0019] The thickness of the polyimide film is preferably 3 to 20 μm, more preferably 4 to 15 μm, and even more preferably 5 to 10 μm. When the thickness of the polyimide film is within this range, the polyimide film is not damaged during the manufacture of the electronic device, the manufacture of the electronic device is easy, and the polyimide film can be stably peeled off from the glass substrate or silicon substrate after the manufacture of the electronic device. The thickness of the polyimide film can be physically measured using a micrometer or the like, or can be obtained by optically observing the thickness using a laser microscope or the like and measuring the height between the top surface of the film and the surface in contact with the glass.
[0020] The peel strength of the polyimide film from a glass substrate or a silicon substrate is preferably 20 gf / cm or less, more preferably 15 gf / cm or less, and even more preferably 10 gf / cm or less. When the peel strength is within this range, the polyimide film adheres closely to the glass substrate or the silicon substrate during the manufacture of the electronic device and does not peel off, and can be stably peeled off from the glass substrate or the silicon substrate after the manufacture of the electronic device.
[0021] The polyimide film of the present invention is excellent in colorless transparency and optical isotropy. The preferable physical properties of the polyimide film of the present invention are as follows.
[0022] The total light transmittance is preferably 88% or more, more preferably 88.5% or more, and even more preferably 89% or more when the film is made into a 10 μm thick film. The yellow index (YI) is preferably 4.0 or less, more preferably 2.5 or less, and even more preferably 2.0 or less when the film is made into a 10 μm thick film. * When a film having a thickness of 10 μm is formed, it is preferably 2.0 or less, more preferably 1.2 or less, and even more preferably 1.0 or less.
[0023] The absolute value of the thickness retardation (Rth) is preferably 100 nm or less, more preferably 60 nm or less, and even more preferably 35 nm or less, when the film has a thickness of 10 μm. When the absolute value is within this range, the optical isotropy is excellent.
[0024] The tensile strength is preferably 60 MPa or more, more preferably 70 MPa or more, and even more preferably 80 MPa or more. The tensile modulus is preferably 2.0 GPa or more, more preferably 2.5 GPa or more, and even more preferably 3.0 GPa or more.
[0025] The glass transition temperature (Tg) of the polyimide resin constituting the polyimide film in the present invention is preferably 230° C. or higher, more preferably 250° C. or higher, and even more preferably 270° C. or higher.
[0026] A preferred example of the polyimide resin that can be used in the present invention is shown below, but the present invention is not limited to this example.
[0027] [Polyimide resin 1] Polyimide resin 1 has a structural unit A1 derived from a tetracarboxylic dianhydride and a structural unit B1 derived from a diamine, in which the structural unit A1 includes a structural unit (A-11) derived from a compound represented by formula (a-11) below, and a structural unit (A-12) derived from a compound represented by formula (a-12) below, and the structural unit B1 includes a structural unit (B-11) derived from a compound represented by formula (b-11) below, and a structural unit (B-12) derived from a compound represented by formula (b-12) below.
[0028] [ka]
[0029] <Structural unit A1> The structural unit A1 is a structural unit derived from a tetracarboxylic dianhydride contained in the polyimide resin 1, and includes a structural unit (A-11) derived from a compound represented by the following formula (a-11) and a structural unit (A-12) derived from a compound represented by the following formula (a-12).
[0030] [ka]
[0031] The compound represented by formula (a-11) is 1,2,4,5-cyclohexanetetracarboxylic dianhydride. The compound represented by formula (a-12) is 4,4'-oxydiphthalic anhydride. The structural unit A1 contains both the structural unit (A-11) and the structural unit (A-12), and thus the film can have improved colorless transparency, optical isotropy, and chemical resistance. The structural unit (A-11) contributes greatly to improving the colorless transparency and optical isotropy, and the structural unit (A-12) contributes greatly to improving the chemical resistance.
[0032] The proportion of the structural unit (A-11) in the structural unit A1 is preferably from 5 to 95 mol %, more preferably from 15 to 95 mol %, even more preferably from 20 to 90 mol %, and particularly preferably from 50 to 90 mol %. The proportion of the structural unit (A-12) in the structural unit A1 is preferably from 5 to 95 mol %, more preferably from 5 to 85 mol %, even more preferably from 10 to 80 mol %, and particularly preferably from 10 to 50 mol %. The total ratio of the structural units (A-11) and (A-12) in the structural unit A1 is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total ratio of the structural units (A-11) and (A-12) is not particularly limited, that is, it is 100 mol%. The structural unit A1 may be composed of only the structural unit (A-11) and the structural unit (A-12).
[0033] The structural unit A1 may contain structural units other than the structural units (A-11) and (A-12). The tetracarboxylic dianhydride that gives such a structural unit is not particularly limited, but includes aromatic tetracarboxylic dianhydrides such as pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 9,9'-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (excluding the compound represented by formula (a-12)); alicyclic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutane tetracarboxylic dianhydride and norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride (excluding the compound represented by formula (a-11)); and aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butane tetracarboxylic dianhydride. In this specification, the term "aromatic tetracarboxylic acid dianhydride" refers to a tetracarboxylic acid dianhydride containing one or more aromatic rings, the term "alicyclic tetracarboxylic acid dianhydride" refers to a tetracarboxylic acid dianhydride containing one or more alicyclic rings but no aromatic rings, and the term "aliphatic tetracarboxylic acid dianhydride" refers to a tetracarboxylic acid dianhydride containing neither an aromatic ring nor an alicyclic ring. The structural units optionally contained in the structural unit A1 (that is, structural units other than the structural units (A-11) and (A-12)) may be of one type, or of two or more types.
[0034] <Structural unit B1> The structural unit B1 is a structural unit derived from a diamine contained in the polyimide resin, and includes a structural unit (B-11) derived from a compound represented by the following formula (b-11) and a structural unit (B-12) derived from a compound represented by the following formula (b-12). [ka]
[0035] The compound represented by formula (b-11) is 3,3'-diaminodiphenyl sulfone. When the structural unit B1 contains the structural unit (B-11), the optical isotropy and chemical resistance of the film can be improved. The compound represented by formula (b-12) is bis[4-(4-aminophenoxy)phenyl]sulfone. When the structural unit B1 contains the structural unit (B-12), the tensile elongation of the film can be improved.
[0036] The proportion of the structural unit (B-11) in the structural unit B1 is preferably from 5 to 95 mol %, more preferably from 15 to 95 mol %, even more preferably from 20 to 90 mol %, and particularly preferably from 50 to 90 mol %. The proportion of the structural unit (B-12) in the structural unit B1 is preferably from 5 to 95 mol %, more preferably from 5 to 85 mol %, even more preferably from 10 to 80 mol %, and particularly preferably from 10 to 50 mol %. The total ratio of the structural units (B-11) and (B-12) in the structural unit B1 is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total ratio of the structural units (B-11) and (B-12) is not particularly limited, that is, it is 100 mol%. The structural unit B1 may be composed of only the structural unit (B-11) and the structural unit (B-12).
[0037] The structural unit B1 may contain a structural unit other than the structural units (B-11) and (B-12). Diamines that provide such structural units are not particularly limited, but include 1,4-phenylenediamine, p-xylylenediamine, 3,5-diaminobenzoic acid, 1,5-diaminonaphthalene, 2,2'-dimethylbiphenyl-4,4'-diamine, 2,2'-bis(trifluoromethyl)benzidine, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminodiphenylsulfone, 4,4'-diaminobenzanilide, 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-inden-5-amine, α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, and the like. aromatic diamines such as 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether, N,N'-bis(4-aminophenyl)terephthalamide, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, 9,9-bis(4-aminophenyl)fluorene, and 4,4'-diamino-2,2'-bistrifluoromethyldiphenyl ether (excluding the compounds represented by formula (b-11) or (b-12)); alicyclic diamines such as 1,3-bis(aminomethyl)cyclohexane and 1,4-bis(aminomethyl)cyclohexane; and aliphatic diamines such as ethylenediamine and hexamethylenediamine. In this specification, an aromatic diamine refers to a diamine containing one or more aromatic rings, an alicyclic diamine refers to a diamine containing one or more alicyclic rings but no aromatic rings, and an aliphatic diamine refers to a diamine containing neither an aromatic ring nor an alicyclic ring. The structural units optionally contained in the structural unit B1 (that is, structural units other than the structural units (B-11) and (B-12)) may be of one type, or of two or more types.
[0038] As the diamine that provides the structural unit optionally contained in the structural unit B1, a compound represented by the following formula (b-13-1), a compound represented by the following formula (b-13-2), a compound represented by the following formula (b-13-3), and a compound represented by the following formula (b-13-4) are preferred. That is, in the polyimide resin of one embodiment of the present invention, the structural unit B1 may further include at least one structural unit (B-13) selected from the group consisting of a structural unit (B-13-1) derived from a compound represented by the following formula (b-13-1), a structural unit (B-13-2) derived from a compound represented by the following formula (b-13-2), a structural unit (B-13-3) derived from a compound represented by the following formula (b-13-3), and a structural unit (B-13-4) derived from a compound represented by the following formula (b-13-4).
[0039] [ka] (In formula (b-13-2), each R is independently a hydrogen atom, a fluorine atom, or a methyl group.)
[0040] The compound represented by formula (b-13-1) is 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether (6FODA). When the structural unit B1 contains the structural unit (B-13-1), the colorless transparency of the film can be improved.
[0041] In formula (b-13-2), R is independently selected from the group consisting of a hydrogen atom, a fluorine atom, and an alkyl group having 1 to 5 carbon atoms, and is a hydrogen atom, a fluorine atom, or a methyl group, and is preferably a hydrogen atom. Examples of the compound represented by formula (b-13-2) include 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(3-fluoro-4-aminophenyl)fluorene, and 9,9-bis(3-methyl-4-aminophenyl)fluorene, and at least one selected from the group consisting of these three compounds is preferred, and 9,9-bis(4-aminophenyl)fluorene is preferred. When the structural unit B1 contains the structural unit (B-13-2), the optical isotropy and heat resistance of the film can be improved.
[0042] The compound represented by formula (b-13-3) is 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane. When the structural unit B1 contains the structural unit (B-13-3), the colorless transparency of the film can be improved.
[0043] The compound represented by formula (b-13-4) is 2,2'-bis(trifluoromethyl)benzidine. When the structural unit B1 contains the structural unit (B-13-4), the colorless transparency, chemical resistance, and mechanical properties of the film can be improved.
[0044] When the structural unit B1 contains the structural unit (B-11), the structural unit (B-12), and the structural unit (B-13), the total proportion of the structural units (B-11) and (B-12) in the structural unit B1 is preferably 70 to 95 mol%, more preferably 75 to 95 mol%, and even more preferably 75 to 90 mol%, and the proportion of the structural unit (B-13) in the structural unit B1 is preferably 5 to 30 mol%, more preferably 5 to 25 mol%, and even more preferably 10 to 25 mol%. The total ratio of the structural unit (B-11), the structural unit (B-12), and the structural unit (B-13) in the structural unit B1 is preferably 75 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total ratio of the structural unit (B-11), the structural unit (B-12), and the structural unit (B-13) is not particularly limited, that is, it is 100 mol%. The structural unit B1 may be composed of only the structural unit (B-11), the structural unit (B-12), and the structural unit (B-13).
[0045] The structural unit (B-13) may be only the structural unit (B-13-1), only the structural unit (B-13-2), only the structural unit (B-13-3), or only the structural unit (B-13-4). In addition, the structural unit (B-13) may be a combination of two or more structural units selected from the group consisting of the structural units (B-13-1) to (B-13-4).
[0046] From the viewpoint of the mechanical strength of the resulting polyimide film, the number average molecular weight of the polyimide resin 1 is preferably 5,000 to 200,000. The number average molecular weight of the polyimide resin can be determined, for example, from a standard polymethyl methacrylate (PMMA) equivalent value measured by gel filtration chromatography.
[0047] The polyimide resin 1 may contain a structure other than a polyimide chain (a structure formed by imide bonding between the structural unit A1 and the structural unit B1). Examples of structures other than a polyimide chain that can be contained in the polyimide resin include structures containing amide bonds. The polyimide resin 1 preferably contains a polyimide chain (a structure formed by imide bonding between the structural unit A1 and the structural unit B1) as a main structure. Therefore, the ratio of the polyimide chain in the polyimide resin 1 is preferably 50 mass % or more, more preferably 70 mass % or more, further preferably 90 mass % or more, and particularly preferably 99 mass % or more.
[0048] [Method of manufacturing polyimide resin 1] Polyimide resin 1 can be produced by reacting a tetracarboxylic acid component containing a compound that provides the above-mentioned structural unit (A-11) and a compound that provides the above-mentioned structural unit (A-12) with a diamine component containing a compound that provides the above-mentioned structural unit (B-11) and a compound that provides the above-mentioned structural unit (B-12).
[0049] Compounds that give the structural unit (A-11) include compounds represented by formula (a-11), but are not limited thereto, and may be derivatives thereof as long as they give the same structural unit. Examples of such derivatives include tetracarboxylic acids (i.e., 1,2,4,5-cyclohexanetetracarboxylic acid) corresponding to the tetracarboxylic dianhydride represented by formula (a-11) and alkyl esters of the tetracarboxylic acid. Compounds that give the structural unit (A-11) are preferably compounds represented by formula (a-11) (i.e., dianhydrides). Similarly, examples of compounds that provide the structural unit (A-12) include compounds represented by formula (a-12), but are not limited thereto and may be derivatives thereof as long as they provide the same structural unit. Examples of such derivatives include tetracarboxylic acids corresponding to the tetracarboxylic dianhydride represented by formula (a-12) and alkyl esters of the tetracarboxylic acid. Compounds that provide the structural unit (A-12) are preferably compounds represented by formula (a-12) (i.e., dianhydrides).
[0050] The tetracarboxylic acid component contains a compound that provides the structural unit (A-11) in an amount of preferably 5 to 95 mol %, more preferably 15 to 95 mol %, even more preferably 20 to 90 mol %, and particularly preferably 50 to 90 mol %. The tetracarboxylic acid component contains a compound that provides the structural unit (A-12) in an amount of preferably 5 to 95 mol %, more preferably 5 to 85 mol %, even more preferably 10 to 80 mol %, and particularly preferably 10 to 50 mol %. The tetracarboxylic acid component contains a compound that gives the structural unit (A-11) and a compound that gives the structural unit (A-12) in a total amount of preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total content ratio of the compound that gives the structural unit (A-11) and the compound that gives the structural unit (A-12) is not particularly limited, that is, it is 100 mol%. The tetracarboxylic acid component may be composed only of a compound that gives the structural unit (A-11) and a compound that gives the structural unit (A-12).
[0051] The tetracarboxylic acid component may contain a compound other than the compound that provides the structural unit (A-11) and the compound that provides the structural unit (A-12). Examples of such compounds include the above-mentioned aromatic tetracarboxylic acid dianhydrides, alicyclic tetracarboxylic acid dianhydrides, and aliphatic tetracarboxylic acid dianhydrides, as well as derivatives thereof (tetracarboxylic acids, alkyl esters of tetracarboxylic acids, etc.). The compound optionally contained in the tetracarboxylic acid component (i.e., compounds other than the compound that provides the structural unit (A-11) and the compound that provides the structural unit (A-12)) may be one type, or two or more types.
[0052] Compounds that provide the structural unit (B-11) include compounds represented by formula (b-11), but are not limited thereto, and may be derivatives thereof as long as they provide the same structural unit. Examples of such derivatives include diisocyanates corresponding to the diamines represented by formula (b-11). Compounds that provide the structural unit (B-11) are preferably compounds represented by formula (b-11) (i.e., diamines). Compounds that provide the structural unit (B-12) include compounds represented by formula (b-12), but are not limited thereto and may be derivatives thereof as long as they provide the same structural unit. Examples of such derivatives include diisocyanates corresponding to the diamines represented by formula (b-12). Compounds that provide the structural unit (B-12) are preferably compounds represented by formula (b-12) (i.e., diamines).
[0053] The diamine component contains the structural unit (B-11) in an amount of preferably 5 to 95 mol %, more preferably 15 to 95 mol %, even more preferably 20 to 90 mol %, and particularly preferably 50 to 90 mol %. The diamine component contains the structural unit (B-12) in an amount of preferably 5 to 95 mol %, more preferably 5 to 85 mol %, even more preferably 10 to 80 mol %, and particularly preferably 10 to 50 mol %. The diamine component contains the structural units (B-11) and (B-12) in total, preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total ratio of the structural units (B-11) and (B-12) is not particularly limited, that is, it is 100 mol%. The diamine component may be composed of only the structural unit (B-11) and the structural unit (B-12).
[0054] The diamine component may contain a compound other than the compound that provides the structural unit (B-11) and the compound that provides the structural unit (B-12). Examples of such compounds include the above-mentioned aromatic diamines, alicyclic diamines, and aliphatic diamines, as well as their derivatives (diisocyanates, etc.). The compound optionally contained in the diamine component (i.e., compounds other than the compound that provides the structural unit (B-11) and the compound that provides the structural unit (B-12)) may be one type, or two or more types.
[0055] As the compound optionally contained in the diamine component, a compound which provides the structural unit (B-13) (i.e., a compound which provides the structural unit (B-13-1), a compound which provides the structural unit (B-13-2), a compound which provides the structural unit (B-13-3), and a compound which provides the structural unit (B-13-4)) is preferred. Compounds that provide the structural unit (B-13) include compounds represented by formula (b-13-1), compounds represented by formula (b-13-2), compounds represented by formula (b-13-3), and compounds represented by formula (b-13-4), but are not limited thereto, and may be derivatives thereof as long as they can form the same structural unit. Examples of such derivatives include diisocyanates corresponding to the diamines represented by formulas (b-13-1) to (b-13-4). Compounds that provide the structural unit (B-13) are preferably compounds represented by formulas (b-13-1) to (b-13-4) (i.e., diamines).
[0056] When the diamine component contains a compound that provides the structural unit (B-11), a compound that provides the structural unit (B-12), and a compound that provides the structural unit (B-13), the diamine component preferably contains a total of 70 to 95 mol %, more preferably 75 to 95 mol %, and even more preferably 75 to 90 mol %, of the compound that provides the structural unit (B-11) and the compound that provides the structural unit (B-12), and preferably contains 5 to 30 mol %, more preferably 5 to 25 mol %, and even more preferably 10 to 25 mol % of the compound that provides the structural unit (B-13). The diamine component contains a compound that gives the structural unit (B-11), a compound that gives the structural unit (B-12), and a compound that gives the structural unit (B-13) in total, preferably 75 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total content ratio of the compound that gives the structural unit (B-11), the compound that gives the structural unit (B-12), and the compound that gives the structural unit (B-13) is not particularly limited, that is, it is 100 mol%. The diamine component may be composed only of a compound that gives the structural unit (B-11), a compound that gives the structural unit (B-12), and a compound that gives the structural unit (B-13).
[0057] The compound that provides the structural unit (B-13) may be only compounds that provide the structural unit (B-13-1), may be only compounds that provide the structural unit (B-13-2), may be only compounds that provide the structural unit (B-13-3), or may be only compounds that provide the structural unit (B-13-4). Furthermore, the compound that provides the structural unit (B-13) may be a combination of two or more compounds selected from the group consisting of compounds that provide the structural units (B-13-1) to (B-13-4).
[0058] The ratio of the amounts of the tetracarboxylic acid component and the diamine component used in the production of the polyimide resin 1 is preferably 0.9 to 1.1 mol of the diamine component per 1 mol of the tetracarboxylic acid component.
[0059] In addition to the above-mentioned tetracarboxylic acid component and diamine component, a terminal blocking agent may be used in the production of the polyimide resin 1. As the terminal blocking agent, monoamines or dicarboxylic acids are preferred. The amount of the terminal blocking agent to be introduced is preferably 0.0001 to 0.1 mol, particularly preferably 0.001 to 0.06 mol, per 1 mol of the tetracarboxylic acid component. As the monoamine terminal blocking agent, for example, methylamine, ethylamine, propylamine, butylamine, benzylamine, 4-methylbenzylamine, 4-ethylbenzylamine, 4-dodecylbenzylamine, 3-methylbenzylamine, 3-ethylbenzylamine, aniline, 3-methylaniline, 4-methylaniline, etc. are recommended. Among these, benzylamine and aniline are preferably used. As the dicarboxylic acid terminal blocking agent, dicarboxylic acids are preferred, and a part of them may be ring-closed. For example, phthalic acid, phthalic anhydride, 4-chlorophthalic acid, tetrafluorophthalic acid, 2,3-benzophenonedicarboxylic acid, 3,4-benzophenonedicarboxylic acid, cyclopentane-1,2-dicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, etc. are recommended. Of these, phthalic acid and phthalic anhydride are preferably used.
[0060] The method for reacting the tetracarboxylic acid component and the diamine component is not particularly limited, and any known method can be used. Specific reaction methods include (1) a method in which a tetracarboxylic acid component, a diamine component, and a reaction solvent are charged into a reactor, and the mixture is stirred at room temperature to 80°C for 0.5 to 30 hours, and then the temperature is raised to carry out the imidization reaction; (2) a method in which a diamine component and a reaction solvent are charged into a reactor and dissolved, and then a tetracarboxylic acid component is charged, and the mixture is stirred at room temperature to 80°C for 0.5 to 30 hours as necessary, and then the temperature is raised to carry out the imidization reaction; and (3) a method in which a tetracarboxylic acid component, a diamine component, and a reaction solvent are charged into a reactor, and the temperature is immediately raised to carry out the imidization reaction.
[0061] The reaction solvent used in the production of the polyimide resin 1 may be any solvent that does not inhibit the imidization reaction and can dissolve the resulting polyimide resin. Examples of the solvent include aprotic solvents, phenol-based solvents, ether-based solvents, and carbonate-based solvents.
[0062] Specific examples of aprotic solvents include amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-methylcaprolactam, 1,3-dimethylimidazolidinone, and tetramethylurea; lactone-based solvents such as γ-butyrolactone and γ-valerolactone; phosphorus-containing amide-based solvents such as hexamethylphosphoric amide and hexamethylphosphine triamide; sulfur-containing solvents such as dimethyl sulfone, dimethyl sulfoxide, and sulfolane; ketone-based solvents such as acetone, cyclohexanone, and methylcyclohexanone; amine-based solvents such as picoline and pyridine; and ester-based solvents such as 2-methoxy-1-methylethyl acetate.
[0063] Specific examples of phenol-based solvents include phenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, and 3,5-xylenol. Specific examples of ether solvents include 1,2-dimethoxyethane, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, bis[2-(2-methoxyethoxy)ethyl]ether, tetrahydrofuran, and 1,4-dioxane. Specific examples of carbonate solvents include diethyl carbonate, methyl ethyl carbonate, ethylene carbonate, and propylene carbonate. Among the above reaction solvents, amide-based solvents and lactone-based solvents are preferred. The above reaction solvents may be used alone or in combination of two or more.
[0064] In the imidization reaction, it is preferable to carry out the reaction while removing water generated during the production using a Dean-Stark apparatus, etc. By carrying out such an operation, it is possible to further increase the degree of polymerization and the imidization rate.
[0065] In the above imidization reaction, a known imidization catalyst can be used, such as a base catalyst or an acid catalyst. Examples of the base catalyst include organic base catalysts such as pyridine, quinoline, isoquinoline, α-picoline, β-picoline, 2,4-lutidine, 2,6-lutidine, trimethylamine, triethylamine, tripropylamine, tributylamine, triethylenediamine, imidazole, N,N-dimethylaniline, and N,N-diethylaniline; and inorganic base catalysts such as potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogencarbonate, and sodium hydrogencarbonate. Examples of the acid catalyst include crotonic acid, acrylic acid, trans-3-hexenoic acid, cinnamic acid, benzoic acid, methylbenzoic acid, oxybenzoic acid, terephthalic acid, benzenesulfonic acid, paratoluenesulfonic acid, naphthalenesulfonic acid, etc. The above imidization catalysts may be used alone or in combination of two or more kinds. Among the above, from the viewpoint of handleability, it is preferable to use a base catalyst, more preferably an organic base catalyst, further preferably triethylamine, and particularly preferably a combination of triethylamine and triethylenediamine.
[0066] The temperature of the imidization reaction is preferably 120 to 250° C., more preferably 160 to 200° C., from the viewpoints of reaction rate and suppression of gelation, etc. The reaction time is preferably 0.5 to 10 hours after the start of distillation of the produced water.
[0067] The solid content concentration during the imidization reaction is preferably 30 to 60 mass%, more preferably 35 to 58 mass%, and particularly preferably 40 to 56 mass%. When the solid content concentration during the imidization reaction is within this range, the imidization reaction proceeds smoothly and water generated during the reaction is easily removed, so that the polymerization degree and the imidization rate can be increased. The solid content concentration during the imidization reaction is a value calculated from the following formula based on the masses of the tetracarboxylic acid component added to the reaction system, the diamine component in the reaction system, and the reaction solvent. Solid content concentration during imidization reaction (mass%)=(total mass of tetracarboxylic acid component and diamine component) / (total mass of tetracarboxylic acid component, diamine component, and reaction solvent)×100
[0068] Another preferred example of the polyimide resin that can be used in the present invention is shown below, but the present invention is not limited to this example.
[0069] [Polyimide resin 2] Polyimide resin 2 has a structural unit A2 derived from a tetracarboxylic dianhydride and a structural unit B2 derived from a diamine, in which structural unit A2 contains a structural unit (A-21) derived from a compound represented by formula (a-21) below and a structural unit (A-22) derived from a compound represented by formula (a-22) below, structural unit B2 contains a structural unit (B-21) derived from a compound represented by formula (b-21) below, and the ratio of structural unit (B-21) in structural unit B2 is 70 mol % or more. [ka]
[0070] <Structural unit A2> The structural unit A2 is a structural unit derived from a tetracarboxylic dianhydride contained in the polyimide resin 2, and includes a structural unit (A-21) derived from a compound represented by formula (a-21) and a structural unit (A-22) derived from a compound represented by formula (a-22). The compound represented by formula (a-21) is the same as the compound represented by formula (a-11) described above. The compound represented by formula (a-22) is the same as the compound represented by formula (a-12) described above. The structural unit A2 contains both the structural unit (A-21) and the structural unit (A-22), and thus the film can have improved colorless transparency, optical isotropy, and chemical resistance. The structural unit (A-21) contributes greatly to improving the colorless transparency and optical isotropy, and the structural unit (A-22) contributes greatly to improving the chemical resistance.
[0071] The proportion of the structural unit (A-21) in the structural unit A2 is preferably from 5 to 95 mol %, more preferably from 15 to 95 mol %, even more preferably from 20 to 90 mol %, and particularly preferably from 50 to 90 mol %. The proportion of the structural unit (A-22) in the structural unit A2 is preferably from 5 to 95 mol %, more preferably from 5 to 85 mol %, even more preferably from 10 to 80 mol %, and particularly preferably from 10 to 50 mol %. The total ratio of the structural units (A-21) and (A-22) in the structural unit A2 is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total ratio of the structural units (A-21) and (A-22) is not particularly limited, that is, it is 100 mol%. The structural unit A2 may be composed of only the structural unit (A-21) and the structural unit (A-22).
[0072] The structural unit A2 may contain structural units other than the structural units (A-21) and (A-22). The tetracarboxylic dianhydride that gives such a structural unit is not particularly limited, but includes aromatic tetracarboxylic dianhydrides such as pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 9,9'-bis(3,4-dicarboxyphenyl)fluorene dianhydride, and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (excluding the compound represented by formula (a-22)); alicyclic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutane tetracarboxylic dianhydride and norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride (excluding the compound represented by formula (a-21)); and aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butane tetracarboxylic dianhydride. The structural units optionally contained in the structural unit A2 (that is, structural units other than the structural units (A-21) and (A-22)) may be of one type, or of two or more types.
[0073] <Structural unit B2> The structural unit B2 is a structural unit derived from a diamine contained in the polyimide resin, and includes a structural unit (B-21) derived from a compound represented by formula (b-21). The compound represented by formula (b-21) is the same as the compound represented by formula (b-11) described above. When the structural unit B2 contains the structural unit (B-21), the optical isotropy and chemical resistance of the film can be improved.
[0074] The ratio of the structural unit (B-21) in the structural unit B2 is 70 mol% or more. The ratio is preferably 75 mol% or more, more preferably 80 mol% or more. The upper limit of the ratio of the structural unit (B-21) may be 90 mol%, 95 mol%, 99 mol%, or 100 mol%. The structural unit B2 may be composed of only the structural unit (B-21).
[0075] The structural unit B2 may contain a structural unit other than the structural unit (B-21). Diamines that provide such a structural unit are not particularly limited, but include 1,4-phenylenediamine, p-xylylenediamine, 3,5-diaminobenzoic acid, 1,5-diaminonaphthalene, 2,2'-dimethylbiphenyl-4,4'-diamine, 2,2'-bis(trifluoromethyl)benzidine, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminodiphenylsulfone, 4,4'-diaminobenzanilide, 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-inden-5-amine, α,α'-bis(4-aminophenyl)-1,4-diisopropyl aromatic diamines such as benzene, N,N'-bis(4-aminophenyl)terephthalamide, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, 9,9-bis(4-aminophenyl)fluorene, and 4,4'-diamino-2,2'-bistrifluoromethyldiphenyl ether (excluding the compound represented by formula (b-21)); alicyclic diamines such as 1,3-bis(aminomethyl)cyclohexane and 1,4-bis(aminomethyl)cyclohexane; and aliphatic diamines such as ethylenediamine and hexamethylenediamine. The structural unit optionally contained in the structural unit B2 (that is, a structural unit other than the structural unit (B-21)) may be of one type, or of two or more types.
[0076] As the diamine that provides the structural unit optionally contained in the structural unit B2, a compound represented by the following formula (b-22-1), a compound represented by the following formula (b-22-2), a compound represented by the following formula (b-22-3), and a compound represented by the following formula (b-22-4) are preferred. That is, in the polyimide resin of one embodiment of the present invention, the structural unit B2 may further include at least one structural unit (B-22) selected from the group consisting of a structural unit (B-22-1) derived from a compound represented by the following formula (b-22-1), a structural unit (B-22-2) derived from a compound represented by the following formula (b-22-2), a structural unit (B-22-3) derived from a compound represented by the following formula (b-22-3), and a structural unit (B-22-4) derived from a compound represented by the following formula (b-22-4). [ka] (In formula (b-22-2), each R is independently a hydrogen atom, a fluorine atom, or a methyl group.)
[0077] The compound represented by formula (b-22-1) is the same as the compound represented by formula (b-13-1) described above. When the structural unit B contains the structural unit (B-22-1), the colorless transparency of the film can be improved.
[0078] The compound represented by formula (b-22-2) is the same as the compound represented by formula (b-13-2) described above, and the preferred range is also the same. When the structural unit B2 contains the structural unit (B-22-2), the optical isotropy and heat resistance of the film can be improved.
[0079] The compound represented by formula (b-22-3) is the same as the compound represented by formula (b-13-3) described above. When the structural unit B2 contains the structural unit (B-22-3), the colorless transparency of the film can be improved.
[0080] The compound represented by formula (b-22-4) is the same as the compound represented by formula (b-13-4) described above. When the structural unit B2 contains the structural unit (B-22-4), the colorless transparency, chemical resistance, and mechanical properties of the film can be improved.
[0081] When the structural unit B2 contains the structural unit (B-21) and the structural unit (B-22), the proportion of the structural unit (B-21) in the structural unit B2 is preferably 70 to 95 mol %, more preferably 75 to 95 mol %, and even more preferably 75 to 90 mol %, and the proportion of the structural unit (B-22) in the structural unit B2 is preferably 5 to 30 mol %, more preferably 5 to 25 mol %, and even more preferably 10 to 25 mol %. The total ratio of the structural unit (B-21) and the structural unit (B-22) in the structural unit B2 is preferably 75 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total ratio of the structural unit (B-21) and the structural unit (B-22) is not particularly limited, that is, it is 100 mol%. The structural unit B may be composed of only the structural unit (B-21) and the structural unit (B-22).
[0082] The structural unit (B-22) may be only the structural unit (B-22-1), only the structural unit (B-22-2), only the structural unit (B-22-3), or only the structural unit (B-22-4). Furthermore, the structural unit (B-22) may be a combination of two or more structural units selected from the group consisting of the structural units (B-22-1) to (B-22-4).
[0083] The number average molecular weight of the polyimide resin 2 is preferably 5,000 to 200,000 from the viewpoint of the mechanical strength of the resulting polyimide film.
[0084] The polyimide resin 2 may contain a structure other than a polyimide chain (a structure formed by imide bonding between the structural unit A2 and the structural unit B2). Examples of structures other than polyimide chains that can be contained in the polyimide resin include structures containing amide bonds. The polyimide resin 2 preferably contains a polyimide chain (a structure formed by imide bonding between the structural unit A2 and the structural unit B2) as a main structure. Therefore, the ratio of the polyimide chain in the polyimide resin 2 is preferably 50 mass % or more, more preferably 70 mass % or more, further preferably 90 mass % or more, and particularly preferably 99 mass % or more.
[0085] [Method of manufacturing polyimide resin 2] The polyimide resin can be produced by reacting a tetracarboxylic acid component containing a compound that provides the above-mentioned structural unit (A-21) and a compound that provides the above-mentioned structural unit (A-22) with a diamine component containing 70 mol % or more of a compound that provides the above-mentioned structural unit (B-21).
[0086] Compounds that provide the structural unit (A-21) include compounds represented by formula (a-21), but are not limited thereto, and may be derivatives thereof as long as they provide the same structural unit. Examples of such derivatives include tetracarboxylic acids (i.e., 1,2,4,5-cyclohexanetetracarboxylic acid) corresponding to the tetracarboxylic dianhydride represented by formula (a-21) and alkyl esters of the tetracarboxylic acid. Compounds that provide the structural unit (A-21) are preferably compounds represented by formula (a-21) (i.e., dianhydrides). Similarly, examples of compounds that provide the structural unit (A-22) include compounds represented by formula (a-22), but are not limited thereto and may be derivatives thereof as long as they provide the same structural unit. Examples of such derivatives include tetracarboxylic acids corresponding to the tetracarboxylic dianhydride represented by formula (a-22) and alkyl esters of the tetracarboxylic acid. Compounds that provide the structural unit (A-22) are preferably compounds represented by formula (a-22) (i.e., dianhydrides).
[0087] The tetracarboxylic acid component contains a compound that provides the structural unit (A-21) in an amount of preferably 5 to 95 mol %, more preferably 15 to 95 mol %, even more preferably 20 to 90 mol %, and particularly preferably 50 to 90 mol %. The tetracarboxylic acid component contains a compound that provides the structural unit (A-22) in an amount of preferably 5 to 95 mol %, more preferably 5 to 85 mol %, even more preferably 10 to 80 mol %, and particularly preferably 10 to 50 mol %. The tetracarboxylic acid component contains a compound that gives the structural unit (A-21) and a compound that gives the structural unit (A-22) in a total amount of preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total content ratio of the compound that gives the structural unit (A-21) and the compound that gives the structural unit (A-22) is not particularly limited, that is, it is 100 mol%. The tetracarboxylic acid component may be composed only of a compound that gives the structural unit (A-21) and a compound that gives the structural unit (A-22).
[0088] The tetracarboxylic acid component may contain a compound other than the compound that provides the structural unit (A-21) and the compound that provides the structural unit (A-22). Examples of such compounds include the above-mentioned aromatic tetracarboxylic acid dianhydrides, alicyclic tetracarboxylic acid dianhydrides, and aliphatic tetracarboxylic acid dianhydrides, as well as derivatives thereof (tetracarboxylic acids, alkyl esters of tetracarboxylic acids, etc.). The compound optionally contained in the tetracarboxylic acid component (i.e., compounds other than the compound that provides the structural unit (A-21) and the compound that provides the structural unit (A-22)) may be one type, or two or more types.
[0089] Compounds that provide the structural unit (B-21) include compounds represented by formula (b-21), but are not limited thereto and may be derivatives thereof as long as they provide the same structural unit. Examples of such derivatives include diisocyanates corresponding to the diamines represented by formula (b-21). Compounds that provide the structural unit (B-21) are preferably compounds represented by formula (b-21) (i.e., diamines).
[0090] The diamine component contains 70 mol% or more of the compound that gives the structural unit (B-21). The diamine component contains preferably 75 mol% or more, more preferably 80 mol% or more of the compound that gives the structural unit (B-21). The upper limit of the content of the compound that gives the structural unit (B-21) may be 90 mol%, 95 mol%, 99 mol%, or 100 mol%. The diamine component may consist of only the compound that gives the structural unit (B-21).
[0091] The diamine component may contain a compound other than the compound that provides the structural unit (B-21). Examples of such a compound include the above-mentioned aromatic diamines, alicyclic diamines, and aliphatic diamines, as well as their derivatives (diisocyanates, etc.). The compound optionally contained in the diamine component (that is, a compound other than the compound that provides the structural unit (B-21)) may be one type, or two or more types.
[0092] As the compound optionally contained in the diamine component, a compound which provides the structural unit (B-22) (i.e., a compound which provides the structural unit (B-22-1), a compound which provides the structural unit (B-22-2), a compound which provides the structural unit (B-22-3), and a compound which provides the structural unit (B-22-4)) is preferred. Compounds that provide the structural unit (B-22) include compounds represented by formula (b-22-1), compounds represented by formula (b-22-2), compounds represented by formula (b-22-3), and compounds represented by formula (b-22-4), but are not limited thereto, and may be derivatives thereof as long as they can form the same structural unit. Examples of such derivatives include diisocyanates corresponding to the diamines represented by formulas (b-22-1) to (b-22-4). Compounds that provide the structural unit (B-22) are preferably compounds represented by formulas (b-22-1) to (b-22-4) (i.e., diamines).
[0093] When the diamine component contains a compound that provides the structural unit (B-21) and a compound that provides the structural unit (B-22), the diamine component preferably contains 70 to 95 mol %, more preferably 75 to 95 mol %, and even more preferably 75 to 90 mol % of the compound that provides the structural unit (B-21), and preferably contains 5 to 30 mol %, more preferably 5 to 25 mol %, and even more preferably 10 to 25 mol % of the compound that provides the structural unit (B-22). The diamine component contains a compound that gives the structural unit (B-21) and a compound that gives the structural unit (B-22) in a total amount of preferably 75 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the total content ratio of the compound that gives the structural unit (B-21) and the compound that gives the structural unit (B-22) is not particularly limited, that is, it is 100 mol%. The diamine component may be composed only of a compound that gives the structural unit (B-21) and a compound that gives the structural unit (B-22).
[0094] The compound that provides the structural unit (B-22) may be only compounds that provide the structural unit (B-22-1), may be only compounds that provide the structural unit (B-22-2), may be only compounds that provide the structural unit (B-22-3), or may be only compounds that provide the structural unit (B-22-4). Furthermore, the compound that provides the structural unit (B-22) may be a combination of two or more compounds selected from the group consisting of compounds that provide the structural units (B-22-1) to (B-22-4).
[0095] The ratio of the amounts of the tetracarboxylic acid component and the diamine component used in the production of the polyimide resin 2 is preferably 0.9 to 1.1 mol of the diamine component per 1 mol of the tetracarboxylic acid component.
[0096] In addition to the above-mentioned tetracarboxylic acid component and diamine component, a terminal blocking agent may be used in the production of the polyimide resin 2. The terminal blocking agent is as described for the polyimide resin 1, and the preferred range is also the same.
[0097] The method for reacting the tetracarboxylic acid component and the diamine component is not particularly limited, and any known method can be used. The specific reaction method is as described for the polyimide resin 1.
[0098] The reaction solvent used in the production of the polyimide resin 2 may be any solvent that does not inhibit the imidization reaction and can dissolve the resulting polyimide. Specific examples of the reaction solvent are as described for the polyimide resin 1, and the preferred ranges are also the same.
[0099] In the imidization reaction, it is preferable to carry out the reaction while removing water generated during the production using a Dean-Stark apparatus, etc. By carrying out such an operation, it is possible to further increase the degree of polymerization and the imidization rate.
[0100] In the above imidization reaction, a known imidization catalyst can be used. Specific examples of the imidization catalyst are as described for the polyimide resin 1, and the preferred range is also the same.
[0101] The temperature of the imidization reaction is preferably 120 to 250° C., more preferably 160 to 200° C., from the viewpoints of reaction rate and suppression of gelation, etc. The reaction time is preferably 0.5 to 10 hours after the start of distillation of the produced water.
[0102] Further, as another preferred example of the polyimide resin that can be used in the present invention, there can be mentioned a polyimide resin obtained from the following copolymer, but the present invention is not limited thereto.
[0103] [Copolymer 3] Copolymer 3 is a copolymer having a structural unit A3 derived from a tetracarboxylic dianhydride and a structural unit B3 derived from a diamine, the structural unit A3 is composed of a structural unit (A-31) derived from an alicyclic tetracarboxylic dianhydride (a-31) and a structural unit (A-32) derived from a tetracarboxylic dianhydride (a-32) other than the alicyclic tetracarboxylic dianhydride (a-31); The structural unit B3 contains a structural unit (B-31) derived from a compound represented by the following formula (b-31): The structural unit (A-32) includes at least one selected from the group consisting of a structural unit (A-32-1) derived from a compound represented by the following formula (a-32-1), a structural unit (A-32-2) derived from a compound represented by the following formula (a-32-2), a structural unit (A-32-3) derived from a compound represented by the following formula (a-32-3), and a structural unit (A-32-4) derived from a compound represented by the following formula (a-32-4), The copolymer has imide repeating structural units formed from a compound that provides the structural unit (A-31) and a compound that provides the structural unit (B-31), and has amic acid repeating structural units formed from a compound that provides the structural unit (A-32) and a compound that provides the structural unit B3.
[0104] [ka]
[0105] <Structural unit A3> The structural unit A3 is a structural unit derived from a tetracarboxylic dianhydride contained in the copolymer 3, and is composed of a structural unit (A-31) derived from an alicyclic tetracarboxylic dianhydride (a-31) and a structural unit (A-32) derived from a tetracarboxylic dianhydride (a-32) other than the alicyclic tetracarboxylic dianhydride (a-31).
[0106] The structural unit (A-31) is a structural unit derived from an alicyclic tetracarboxylic dianhydride (a-31). From the viewpoints of high transparency, high heat resistance, and low residual stress, the structural unit (A-31) preferably contains a structural unit (A-31-1) derived from a compound represented by the following formula (a-31-1): The compound represented by formula (a-31-1) is norbornane-2-spiro-α-cyclopentanone-α'-spiro-2″-norbornane-5,5″,6,6″-tetracarboxylic dianhydride.
[0107] [ka]
[0108] The ratio of the structural unit (A-31-1) in the structural unit (A-31) is preferably 45 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. There is no particular upper limit to this ratio, and it is 100 mol%. The structural unit (A-31) may have a structural unit derived from an alicyclic tetracarboxylic dianhydride other than the compound represented by formula (a-31-1). Examples of such alicyclic tetracarboxylic dianhydrides include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, and dicyclohexyl tetracarboxylic dianhydride. The alicyclic tetracarboxylic dianhydrides (a-31) may be used alone or in combination of two or more.
[0109] The structural unit (A-32) is a structural unit derived from a tetracarboxylic dianhydride (a-32) other than the alicyclic tetracarboxylic dianhydride (a-31). The tetracarboxylic dianhydride (a-32) may be at least one selected from the group consisting of aromatic tetracarboxylic dianhydrides and aliphatic tetracarboxylic dianhydrides, and preferably contains an aromatic tetracarboxylic dianhydride. That is, the structural unit (A-32) preferably contains a structural unit derived from an aromatic tetracarboxylic dianhydride. From the standpoint of high heat resistance and low residual stress, the structural unit (A-32) includes at least one selected from the group consisting of a structural unit (A-32-1) derived from a compound represented by the following formula (a-32-1), a structural unit (A-32-2) derived from a compound represented by the following formula (a-32-2), a structural unit (A-32-3) derived from a compound represented by the following formula (a-32-3), and a structural unit (A-32-4) derived from a compound represented by the following formula (a-32-4).
[0110] [ka]
[0111] The compound represented by formula (a-32-1) is biphenyltetracarboxylic dianhydride (BPDA), and specific examples thereof include 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA) represented by the following formula (a-32-1s), 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA) represented by the following formula (a-32-1a), and 2,2',3,3'-biphenyltetracarboxylic dianhydride (i-BPDA) represented by the following formula (a-32-1i). Among these, 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA) represented by the following formula (a-32-1s) is preferred.
[0112] [ka]
[0113] The compound represented by formula (a-32-2) is p-phenylenebis(trimellitate)dianhydride (TAHQ).
[0114] The compound represented by formula (a-32-3) is oxydiphthalic anhydride (ODPA), and specific examples thereof include 4,4'-oxydiphthalic anhydride (s-ODPA) represented by the following formula (a-32-3s), 3,4'-oxydiphthalic anhydride (a-ODPA) represented by the following formula (a-32-3a), and 3,3'-oxydiphthalic anhydride (i-ODPA) represented by the following formula (a-32-3i). Among these, 4,4'-oxydiphthalic anhydride (s-ODPA) represented by the following formula (a-32-3s) is preferred.
[0115] [ka]
[0116] The compound represented by formula (a-32-4) is pyromellitic dianhydride (PMDA).
[0117] From the standpoint of high heat resistance and low residual stress, the structural unit (A-32) preferably includes at least one selected from the group consisting of the structural unit (A-32-1) and the structural unit (A-32-2). The structural unit (A-32-1) is preferred from the viewpoints of improving the heat resistance and thermal stability of the film and further reducing residual stress, while the structural unit (A-32-2) is preferred from the viewpoints of reducing YI and achieving superior colorless transparency.
[0118] The tetracarboxylic dianhydride (a-32) may contain tetracarboxylic dianhydrides other than the compounds represented by formulas (a-32-1) to (a-32-4). Examples of such tetracarboxylic dianhydrides include aromatic tetracarboxylic dianhydrides such as 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, and the compound represented by the following formula (a-32-5); and aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butanetetracarboxylic dianhydride. Among these, aromatic tetracarboxylic dianhydrides are preferred. The tetracarboxylic dianhydrides (a-32) may be used alone or in combination of two or more.
[0119] [ka]
[0120] The ratio of the structural units (A-32-1) to (A-32-4) in the structural unit (A-32) is preferably 45 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. There is no particular upper limit to this ratio, that is, it is 100 mol%. The structural unit (A-32) may contain at least one selected from the structural units (A-32-1) to (A-32-4), and may be composed of only one selected from the structural units (A-32-1) to (A-32-4). When the structural unit (A-32) contains two or more structural units selected from the structural units (A-32-1) to (A-32-4), there are no particular limitations on the ratio of the structural units in the structural unit (A-32), and any ratio can be used.
[0121] In the structural unit A3, the molar ratio of the structural unit (A-31) to the structural unit (A-32) [(A-31) / (A-32)] is preferably 10 / 90 to 90 / 10, more preferably 30 / 70 to 85 / 15, and even more preferably 50 / 50 to 80 / 20. The ratio of the aromatic tetracarboxylic dianhydride-derived structural units in the structural unit (A-32) is preferably 45 mol% or more, more preferably 60 mol% or more, and even more preferably 85 mol% or more. There is no particular upper limit to the total content ratio, i.e., 100 mol%.
[0122] <Structural unit B3> The structural unit B3 is a structural unit derived from a diamine contained in the copolymer of the present invention, and contains a structural unit (B-31) derived from a compound represented by the following formula (b-31): By containing the structural unit (B-31) in the structural unit B, it is possible to achieve both excellent transparency and low residual stress and low retardation properties.
[0123] [ka]
[0124] The compound represented by formula (b-31) is the same as the compound represented by formula (b-13-1) described above.
[0125] It is preferable that the structural unit B3 further contains a structural unit (B-32) derived from a compound represented by the following general formula (b-32): When the structural unit B3 contains the structural unit (B-32), the residual stress is reduced.
[0126] [ka]
[0127] In formula (b-32), Z 1 and Z 2 each independently represents a divalent aliphatic group or a divalent aromatic group; R 1 and R 2 each independently represents a monovalent aromatic group or a monovalent aliphatic group; R 3 and R 4 each independently represents a monovalent aliphatic group; R 5 and R 6 each independently represents a monovalent aliphatic group or a monovalent aromatic group, m and n each independently represent an integer of 1 or more, and the sum of m and n represents an integer of 2 to 1000. 1 and R 2 At least one of these represents a monovalent aromatic group. In formula (b-32), the two or more different repeating units described in parallel in brackets [ ] may be repeated in any form and order of random, alternating, or block.
[0128] In formula (b-32), Z 1 and Z 2 The divalent aliphatic group or divalent aromatic group in may be substituted with a fluorine atom. Examples of the divalent aliphatic group include divalent saturated or unsaturated aliphatic groups having 1 to 20 carbon atoms. The divalent aliphatic group preferably has 3 to 20 carbon atoms. Examples of the divalent saturated aliphatic group include alkylene groups having 1 to 20 carbon atoms, such as a methylene group, an ethylene group, a propylene group, a trimethylene group, a tetramethylene group, a hexamethylene group, an octamethylene group, a decamethylene group, and a dodecamethylene group. The divalent unsaturated aliphatic group may be an alkylene group having 2 to 20 carbon atoms, such as a vinylene group, a propenylene group, or an alkylene group having an unsaturated double bond at a terminal. Examples of the divalent aromatic group include an arylene group having 6 to 20 carbon atoms and an aralkylene group having 7 to 20 carbon atoms. 1 and Z 2 Specific examples of the arylene group having 6 to 20 carbon atoms in the formula include an o-phenylene group, an m-phenylene group, a p-phenylene group, a 4,4'-biphenylylene group, and a 2,6-naphthylene group. Z 1 and Z 2 As the alkyl group, a trimethylene group or a p-phenylene group is particularly preferable, and a trimethylene group is more preferable.
[0129] In formula (b-32), R 1 ~R 6 In the above, examples of the monovalent aliphatic group include monovalent saturated or unsaturated aliphatic groups. Examples of the monovalent saturated aliphatic group include alkyl groups having 1 to 22 carbon atoms, such as methyl, ethyl, and propyl groups. Examples of the monovalent unsaturated aliphatic group include alkenyl groups having 2 to 22 carbon atoms, such as vinyl and propenyl groups. These groups may be substituted with a fluorine atom. R in formula (b-32) 1 , R 2 , R 5 and R 6 Examples of the monovalent aromatic group in the formula (I) include an aryl group having 6 to 20 carbon atoms, an aryl group having 7 to 30 carbon atoms and substituted with an alkyl group, and an aralkyl group having 7 to 30 carbon atoms. As the monovalent aromatic group, an aryl group is preferable, and a phenyl group is more preferable. R 1 and R 2 At least one of R represents a monovalent aromatic group.1 and R 2 are preferably both monovalent aromatic groups, and R 1 and R 2 More preferably, both are phenyl groups. R 3 and R 4 As the alkyl group, an alkyl group having 1 to 6 carbon atoms is preferable, and a methyl group is more preferable. R 5 and R 6 As the group, a monovalent aliphatic group is preferable, and a methyl group is more preferable.
[0130] In formula (b-32), m represents the number of repetitions of the siloxane unit to which at least one monovalent aromatic group is bonded, and n represents the number of repetitions of the siloxane unit to which a monovalent aliphatic group is bonded. m and n each independently represent an integer of 1 or more, and the sum of m and n (m+n) represents an integer of 2 to 1000. The sum of m and n is preferably an integer of 3 to 500, more preferably an integer of 3 to 100, and even more preferably an integer of 3 to 50. The ratio of m / n is preferably from 50 / 50 to 99 / 1, more preferably from 60 / 40 to 90 / 10, and further preferably from 70 / 30 to 80 / 20.
[0131] The functional group equivalent of the compound represented by formula (b-32) is preferably 150 to 5,000 g / mol, more preferably 400 to 4,000 g / mol, and even more preferably 500 to 3,000 g / mol. The functional group equivalent means the mass of the compound represented by formula (b-32) per mole of the functional group.
[0132] The content of the polyorganosiloxane unit relative to the total of the structural unit A3 and the structural unit B3 is preferably 5 to 45 mass%, more preferably 7 to 40 mass%, and even more preferably 10 to 35 mass%. When the content of the polyorganosiloxane unit is within the above range, low retardation and low residual stress can be achieved at the same time to a higher degree. The polyorganosiloxane unit has the same meaning as the structural unit (B-32), and the content of the polyorganosiloxane unit relative to the total of the structural units A3 and B3 is calculated from the mass ratio of the compound that gives the structural unit (B-32), preferably the compound represented by formula (b-32), to the total amount of the raw materials that give the structural units A3 and B3.
[0133] Commercially available compounds of the formula (b-32) include "X-22-9409" and "X-22-1660B-3" manufactured by Shin-Etsu Chemical Co., Ltd.
[0134] It is preferable that the structural unit B3 further contains a structural unit (B-33) derived from a compound represented by the following formula (b-33). [ka]
[0135] The compound represented by formula (b-33) is the same as the compound represented by formula (b-13-2) described above, and the preferred range is also the same. The copolymer of the present invention has improved transparency and heat resistance due to the inclusion of the structural unit (B-33).
[0136] The ratio of the structural unit (B-31) in the structural unit B3 is preferably 45 mol% or more, more preferably 48 mol% or more, even more preferably 85 mol% or more, still more preferably 88 mol% or more, and is preferably 100 mol% or less, more preferably 99.5 mol% or less, even more preferably 99.0 mol% or less. The structural unit B3 may be composed only of the structural unit (B-31). When the structural unit B3 contains the structural unit (B-32), the proportion of the structural unit (B-32) in the structural unit B3 is preferably 0.01 to 15.0 mol %, more preferably 0.5 to 12.0 mol %, and even more preferably 1.0 to 8.0 mol %. When the structural unit B3 contains the structural unit (B-33), the ratio of the structural unit (B-3) in the structural unit B3 is, from the viewpoint of low residual stress, preferably 5 mol % or more, more preferably 10 mol % or more, even more preferably 25 mol % or more, and preferably 65 mol % or less, more preferably 55 mol % or less, even more preferably 50 mol % or less. When the structural unit B3 contains the structural unit (B-33), the total ratio of the structural units (B-31) and (B-33) in the structural unit B3 is preferably 85.0 to 100 mol%, more preferably 88.0 to 99.5 mol%, and even more preferably 92.0 to 99.0 mol%. When the structural unit B3 does not contain the structural unit (B-33), the ratio of the structural unit (B-31) in the structural unit B3 is preferably in the same range as above. The total content of the structural units (B-31) to (B-33) in the structural unit B3 is preferably 45 to 100 mol %, more preferably 60 to 100 mol %, even more preferably 85 to 100 mol %, and especially preferably 100 mol %.
[0137] The structural unit B3 may include structural units other than the structural units (B-31) to (B-33). Diamines that provide such structural units include, but are not limited to, 1,4-phenylenediamine, p-xylylenediamine, 3,5-diaminobenzoic acid, 1,5-diaminonaphthalene, 2,2'-dimethylbiphenyl-4,4'-diamine, 2,2'-bis(trifluoromethyl)benzidine, 2,2'-dimethylbiphenyl-4,4'-diamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminobenzanilide, 3,4'-diaminodiphenyl ether, 1-(4-aminophenyl)-2,3-dihydro-1,3,3- aromatic diamines such as trimethyl-1H-inden-5-amine, α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, N,N'-bis(4-aminophenyl)terephthalamide, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and 1,4-bis(4-aminophenoxy)benzene; alicyclic diamines such as 1,3-bis(aminomethyl)cyclohexane and 1,4-bis(aminomethyl)cyclohexane; and aliphatic diamines such as ethylenediamine and hexamethylenediamine. The structural units other than the structural units (B-31) to (B-33) optionally contained in the structural unit B3 may be of one type, or of two or more types. It is preferable that the structural unit B3 does not contain any structural units other than the structural units (B-31) to (B-33). In particular, from the viewpoint of realizing low retardation, it is preferable that the structural unit B3 does not contain any structural units derived from 2,2'-bis(trifluoromethyl)benzidine.
[0138] <Imide repeating unit / Amic acid repeating unit> Copolymer 3 has an imide repeating structural unit formed from a compound that provides the structural unit (A-31) and a compound that provides the structural unit (B-31), and an amic acid repeating structural unit formed from a compound that provides the structural unit (A-32) and a compound that provides the structural unit B3. Copolymer 3 may have an imide repeating unit formed from a compound other than the compound that provides the structural unit (A-31) and a compound that provides the structural unit B3, or an imide repeating unit formed from a compound that provides the structural unit (A-31) and a compound other than the compound that provides the structural unit (B-31). Similarly, copolymer 3 may have an amic acid repeating unit formed from a compound other than the compound that provides the structural unit (A-32) and a compound that provides the structural unit B3.
[0139] [Production method of copolymer 3] Copolymer 3 can be produced by reacting a tetracarboxylic acid component consisting of a compound that provides the structural unit (A-31) and a compound that provides the structural unit (A-32) with a diamine component that includes a compound that provides the structural unit B3, which contains the structural unit (B-31). Copolymer 3 is preferably produced by a method having the following steps 1 and 2. Step 1: A step of reacting a compound that provides the structural unit (A-31) with a compound that provides the structural unit (B-31) to obtain an oligomer having imide repeating structural units. Step 2: A step of reacting the oligomer obtained in step 1 with a compound that provides the structural unit (A-32) and a compound that provides the structural unit B3 to obtain a copolymer 3 having imide repeating structural units and amic acid repeating structural units. By the production method including the above steps 1 and 2, it is possible to produce the copolymer 3 which is excellent in colorless transparency and heat resistance, and is capable of forming a film having low retardation and low residual stress. The method for producing the copolymer 3 will be described below.
[0140] <Tetracarboxylic acid component> Compounds that give the structural unit (A-31) include, but are not limited to, alicyclic tetracarboxylic dianhydrides (a-31), and may be derivatives thereof as long as they give the same structural unit. Examples of such derivatives include alicyclic tetracarboxylic acids corresponding to the alicyclic tetracarboxylic dianhydrides (a-31) and alkyl esters of the alicyclic tetracarboxylic acids. Compounds that give the structural unit (A-31) are preferably alicyclic tetracarboxylic dianhydrides (a-31). Similarly, examples of compounds that provide the structural unit (A-32) include, but are not limited to, tetracarboxylic dianhydrides (a-32), and may be derivatives thereof as long as they provide the same structural unit. Examples of such derivatives include tetracarboxylic acids corresponding to the tetracarboxylic dianhydrides (a-32) and alkyl esters of the tetracarboxylic acids. The compound that provides the structural unit (A-32) is preferably tetracarboxylic dianhydrides (a-32).
[0141] In the tetracarboxylic acid component, the molar ratio of the compound that provides the structural unit (A-31) to the compound that provides the structural unit (A-32) [(A-31) / (A-32)] is preferably 10 / 90 to 90 / 10, more preferably 30 / 70 to 85 / 15, and even more preferably 50 / 50 to 80 / 20.
[0142] The compound that gives the structural unit (A-31) is preferably a compound that gives the structural unit (A-31-1).The ratio of the compound that gives the structural unit (A-31-1) in the compounds that give the structural unit (A-31) is preferably 45 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more.The upper limit of the ratio is not particularly limited, that is, it is 100 mol%. The compound that gives the structural unit (A-32) is preferably one or more selected from the group consisting of compounds that give the structural unit (A-32-1), compounds that give the structural unit (A-32-2), compounds that give the structural unit (A-32-3), and compounds that give the structural unit (A-32-4). The total ratio of the compounds that give the structural units (A-32-1) to (A-32-4) among the compounds that give the structural unit (A-32) is preferably 45 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and particularly preferably 99 mol% or more. There is no particular upper limit to this ratio, that is, it is 100 mol%. The tetracarboxylic acid component may contain compounds other than the compounds that provide the structural units (A-31-1), (A-32-1), (A-32-2), (A-32-3), and (A-32-4), and such compounds may be one type or two or more types.
[0143] <Diamine component> The compound that gives the structural unit B3 may be a diamine, but is not limited thereto, and may be a derivative thereof as long as it gives the same structural unit. The derivative may be a diisocyanate corresponding to the diamine. The compound that gives the structural unit B3 is preferably a diamine. The compound that provides the structural unit (B-31) is preferably a compound represented by formula (b-31) (i.e., a diamine).Similarly, the compound that provides the structural unit (B-32) is preferably a compound represented by general formula (b-32) (i.e., a diamine), and the compound that provides the structural unit (B-33) is preferably a compound represented by formula (b-33) (i.e., a diamine).
[0144] The diamine component contains a compound that provides the structural unit (B-31) in an amount of preferably 45 mol% or more, more preferably 48 mol% or more, even more preferably 85 mol% or more, still more preferably 88 mol% or less, and preferably 100 mol% or less, more preferably 99.5 mol% or less, even more preferably 99.0 mol% or less. The diamine component may consist of only a compound that provides the structural unit (B-31). When a compound that provides the structural unit (B-32) is contained as a diamine component, the compound that provides the structural unit (B-32) is preferably contained in an amount of 0.01 to 15.0 mol %, more preferably 0.5 to 12.0 mol %, and even more preferably 1.0 to 8.0 mol % of the total diamine components. When a compound that provides the structural unit (B-33) is contained as a diamine component, the compound that provides the structural unit (B-33) preferably accounts for 5 to 65 mol %, more preferably 10 to 55 mol %, and even more preferably 25 to 50 mol % of the total diamine components. The diamine component may be a combination of one or more compounds selected from the group consisting of a compound that provides the structural unit (B-31) and a compound that provides the structural unit (B-32) and a compound that provides the structural unit (B-33).
[0145] The total content of the compound that provides the structural unit (B-31), the compound that provides the structural unit (B-32), and the compound that provides the structural unit (B-33) is preferably 45 mol% or more, more preferably 60 mol% or more, and even more preferably 85 mol% or more, based on the total diamine components. There is no particular upper limit to the total content, and it is 100 mol%.
[0146] The diamine component may contain a compound that provides the structural unit B3 other than the compound that provides the structural unit (B-31), the compound that provides the structural unit (B-32), and the compound that provides the structural unit (B-33). Examples of such compounds include the above-mentioned aromatic diamines, alicyclic diamines, and aliphatic diamines, as well as their derivatives (diisocyanates, etc.). The compound other than the compound that gives the structural units (B-31) to (B-33) that is optionally contained in the diamine component may be one type, or two or more types.
[0147] The ratio of the amounts of the tetracarboxylic acid component and the diamine component used in the production of the copolymer 3 is preferably 0.9 to 1.1 mol of the diamine component per 1 mol of the tetracarboxylic acid component.
[0148] <Solvent> The solvent used in the production of copolymer 3 may be any solvent capable of dissolving the copolymer produced. Specific examples of the reaction solvent are as described for polyimide resin 1. Among the above reaction solvents, amide-based solvents or lactone-based solvents are preferred, amide-based solvents are more preferred, and N-methyl-2-pyrrolidone is even more preferred. The above reaction solvents may be used alone or in combination of two or more.
[0149] <Process 1> Step 1 is a step in which a compound that provides the structural unit (A-31) is reacted with a compound that provides the structural unit (B-31) to obtain an oligomer having imide repeating structural units. The tetracarboxylic acid component used in step 1 includes a compound that provides the structural unit (A-31). When the structural unit (A-31) includes the structural unit (A-31-1), it is preferable to use the entire amount of the compound that provides the structural unit (A-31-1) in step 1. The diamine component used in step 1 includes a compound that provides the structural unit (B-31), and may include a diamine component other than the compound that provides the structural unit (B-31) within a range that does not impair the effects of the present invention. Examples of such compounds include a compound that provides the structural unit (B-33). The ratio of the amounts of the components used in step 1 is preferably such that the diamine component used in step 1 is 0.9 to 1.1 mol, and more preferably 1.0 to 1.1 mol, relative to the compound that provides the structural unit (A-31).
[0150] There are no particular limitations on the method for reacting a tetracarboxylic acid component containing a compound that gives the structural unit (A-31) with a diamine component containing a compound that gives the structural unit (B-31) to obtain an oligomer in step 1, and any known method can be used. Specific reaction methods are as described for polyimide resin 1.
[0151] In the above imidization reaction, a known imidization catalyst can be used. Specific examples of the imidization catalyst are as described for the polyimide resin 1, and the preferred range is also the same.
[0152] The temperature of the imidization reaction is preferably 120 to 250° C., more preferably 160 to 200° C., from the viewpoints of reaction rate and suppression of gelation, etc. The reaction time is preferably 0.5 to 10 hours after the start of distillation of the produced water.
[0153] The oligomer obtained in step 1 has imide repeating structural units formed from the compound that provides the structural unit (A-31) and the compound that provides the structural unit (B-31). The oligomer obtained in step 1 preferably has amino groups at both ends of the main molecular chain. The above method provides a solution containing an oligomer dissolved in a solvent. The solution containing the oligomer obtained in step 1 may contain at least a portion of the components used as the tetracarboxylic acid component or the diamine component in step 1 as unreacted monomers, as long as the effects of the present invention are not impaired.
[0154] <Process 2> Step 2 is a step of reacting the oligomer obtained in step 1 with a compound that provides the structural unit (A-32) and a compound that provides the structural unit B3 to obtain a copolymer having imide repeating structural units and amic acid repeating structural units. The tetracarboxylic acid component used in step 2 contains a compound that gives the structural unit (A-32), and may contain a compound that gives the structural unit (A-31) to the extent that the effects of the present invention are not impaired. However, it is preferable that the tetracarboxylic acid component used in step 2 does not contain a compound that gives the structural unit (A-31-1). It is also preferable that the entire amount of the compound that gives the structural unit (A-32) is used in step 2. The diamine component used in step 2 is a compound that gives the structural unit B3. The diamine component used in step 2 refers to the compounds that give the structural unit B3 in the raw material monomers of the copolymer of the present invention, excluding the diamine component that constitutes the oligomer obtained in step 1. The unreacted diamine component remaining in the solution containing the oligomer obtained in step 1 may be used as the diamine component in step 2. The diamine component used in step 2 preferably contains at least a compound that gives the structural unit (B-31). When a compound that gives the structural unit (B-32) is used, it is preferable to use the entire amount in step 2.
[0155] There are no particular limitations on the method for reacting a tetracarboxylic acid component containing a compound that provides the structural unit (A-32), a diamine component containing a compound that provides the structural unit B3, and the oligomer obtained in step 1 to obtain a copolymer in step 2, and any known method can be used. Specific reaction methods include (1) a method in which the oligomer obtained in step 1, the tetracarboxylic acid component, the diamine component, and the solvent are charged into a reactor and stirred at 0 to 120°C, preferably 5 to 80°C, for 1 to 72 hours, and (2) a method in which the oligomer obtained in step 1, the diamine component, preferably the diamine component other than the compound that gives the structural unit (B-32), and the solvent are charged into a reactor and dissolved, and then the tetracarboxylic acid component is charged and stirred at 0 to 120°C, preferably 5 to 80°C, for 1 to 72 hours, and then the diamine component, preferably the compound that gives the structural unit (B-32), and the solvent are charged and stirred at 0 to 120°C, preferably 15 to 80°C, for 0.5 to 10 hours. When the diamine component contains a compound that gives the structural unit (B-32), the production method (2) is preferred among the above. When the reaction is carried out at 80°C or lower, the molecular weight of the copolymer obtained in step 2 does not vary depending on the temperature history during polymerization, and the progress of thermal imidization can be suppressed, so that the copolymer can be stably produced.
[0156] Copolymer 3 is a copolymer having an amic acid repeating structural unit and an imide repeating structural unit, and is a product of a polyaddition reaction between the tetracarboxylic acid component in step 2, the diamine component in step 2, and the oligomer obtained in step 1. Copolymer 3 has imide repeating structural units formed in step 1 from the compound that provides structural unit (A-31) and the compound that provides structural unit (B-31), and has amic acid repeating structural units formed in step 2 from the compound that provides structural unit (A-32) and the compound that provides structural unit B3.
[0157] By the above method, a copolymer solution containing the copolymer 3 dissolved in the solvent is obtained. The concentration of the copolymer in the obtained copolymer solution is usually in the range of 1 to 50% by mass, preferably 3 to 35% by mass, and more preferably 10 to 30% by mass.
[0158] From the viewpoint of the mechanical strength of the resulting polyimide film, the number average molecular weight of copolymer 3 is preferably 5,000 to 500,000. The number average molecular weight of copolymer 3 can be determined, for example, from a standard polymethyl methacrylate (PMMA)-equivalent value measured by gel filtration chromatography.
[0159] [Manufacturing method of polyimide film] The method for producing the polyimide film of the present invention is not particularly limited, and a known method can be used, for example, a method in which a polyimide varnish is applied to a smooth support such as a glass plate, a metal plate, or a plastic plate, or formed into a film, and then organic solvents such as a reaction solvent and a dilution solvent contained in the varnish are removed by heating.
[0160] Examples of a method for applying the varnish include known application methods such as spin coating, slit coating, blade coating, etc. Among these, slit coating is preferred from the viewpoint of workability, since it controls the intermolecular orientation and improves chemical resistance. A method for removing the organic solvent contained in the varnish by heating is preferably to evaporate the organic solvent at a temperature of 150°C or less to make it tack-free, and then to dry it at a temperature equal to or higher than the boiling point of the organic solvent used (not particularly limited, but preferably 200 to 500°C). It is also preferable to dry it in an air atmosphere or a nitrogen atmosphere. The pressure of the drying atmosphere may be reduced pressure, normal pressure, or increased pressure.
[0161] <Polyimide varnish> The polyimide varnish is prepared by dissolving a polyimide resin in an organic solvent. That is, the polyimide varnish contains a polyimide resin and an organic solvent, and the polyimide resin is dissolved in the organic solvent. The organic solvent is not particularly limited as long as it dissolves the polyimide resin. However, it is preferable to use the above-mentioned compounds as reaction solvents used in the production of the polyimide resin, either alone or in combination of two or more kinds. The polyimide varnish may be a polyimide solution itself in which a polyimide resin obtained by polymerization is dissolved in a reaction solvent, or may be a polyimide solution to which a dilution solvent is further added.
[0162] The polyimide resins 1 and 2 are soluble in solvents, and therefore can be made into a highly concentrated varnish that is stable at room temperature. The polyimide varnish preferably contains 5 to 40 mass % of the polyimide resin 1 or 2, and more preferably contains 10 to 30 mass %. The viscosity of the polyimide varnish is preferably 1 to 200 Pa·s, more preferably 1.5 to 100 Pa·s, and even more preferably 2 to 100 Pa·s. The viscosity of the polyimide varnish is a value measured at 25°C using an E-type viscometer. The polyimide varnish may also contain various additives, such as inorganic fillers, adhesion promoters, release agents, flame retardants, UV stabilizers, surfactants, leveling agents, defoamers, fluorescent brightening agents, crosslinking agents, polymerization initiators, and photosensitizers, as long as the additives do not impair the required properties of the polyimide film. The method for producing the polyimide varnish is not particularly limited, and any known method can be applied.
[0163] <Polyamic acid varnish> The polyimide film can also be produced using a polyamic acid varnish prepared by dissolving polyamic acid in an organic solvent. The polyamic acid contained in the polyamic acid varnish is preferably a precursor of polyimide resin 1 or 2. The polyamic acid, which is a precursor of polyimide resin 1, is a product of a polyaddition reaction between a tetracarboxylic acid component containing a compound that gives the above-mentioned structural unit (A-11) and a compound that gives the above-mentioned structural unit (A-12), and a diamine component containing a compound that gives the above-mentioned structural unit (B-11) and a compound that gives the above-mentioned structural unit (B-12). The polyamic acid, which is a precursor of polyimide resin 2, is a product of a polyaddition reaction between a tetracarboxylic acid component containing a compound that gives the above-mentioned structural unit (A-21) and a compound that gives the above-mentioned structural unit (A-22), and a diamine component containing 70 mol% or more of a compound that gives the above-mentioned structural unit (B-21). The final product, polyimide resin 1 or 2, is obtained by imidizing (dehydrating and ring-closing) these polyamic acids. As the organic solvent contained in the polyamic acid varnish, an organic solvent contained in a polyimide varnish can be used. In the present invention, the polyamic acid varnish may be a polyamic acid solution itself obtained by subjecting a tetracarboxylic acid component and a diamine component to a polyaddition reaction in a reaction solvent, or may be a polyamic acid solution to which a dilution solvent has been further added.
[0164] The method for producing a polyimide film using the polyamic acid varnish is not particularly limited, and a known method can be used.For example, the polyamic acid varnish is applied to a smooth support such as a glass plate, a metal plate, or a plastic plate, or formed into a film, and the organic solvent contained in the varnish, such as a reaction solvent or a dilution solvent, is removed by heating to obtain a polyamic acid film, and the polyamic acid in the polyamic acid film is imidized by heating, thereby producing a polyimide film. The heating temperature when the polyamic acid varnish is dried to obtain a polyamic acid film is preferably 50 to 120° C. The heating temperature when the polyamic acid is imidized by heating is preferably 200 to 400° C. The imidization method is not limited to thermal imidization, and chemical imidization can also be applied.
[0165] <Copolymer varnish> The polyimide film can also be produced by using a copolymer varnish obtained by dissolving the above-mentioned copolymer 3 in an organic solvent. The copolymer varnish is obtained by dissolving the copolymer 3, which is a precursor of a polyimide resin, in an organic solvent. That is, the copolymer varnish contains the copolymer 3 and an organic solvent, and the copolymer 3 is dissolved in the organic solvent. The organic solvent is not particularly limited as long as it dissolves copolymer 3. However, it is preferable to use the above-mentioned compounds alone or in a mixture of two or more kinds as the solvent used in the production of copolymer 3. The copolymer varnish may be the above-mentioned copolymer solution itself, or may be the copolymer solution to which a dilution solvent has been further added.
[0166] The copolymer varnish may further contain an imidization catalyst and a dehydration catalyst from the viewpoint of efficiently proceeding with the imidization of the amide acid moiety in the copolymer 3. The imidization catalyst may be an imidization catalyst having a boiling point of 40°C or more and 180°C or less, and an amine compound having a boiling point of 180°C or less is preferred. If the imidization catalyst has a boiling point of 180°C or less, there is no risk of the film being colored and its appearance being impaired when dried at a high temperature after film formation. In addition, if the imidization catalyst has a boiling point of 40°C or more, the possibility of volatilization before imidization has progressed sufficiently can be avoided. Examples of amine compounds suitable for use as the imidization catalyst include pyridine and picoline. The imidization catalysts may be used alone or in combination of two or more. Examples of the dehydration catalyst include acid anhydrides such as acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, and trifluoroacetic anhydride; carbodiimide compounds such as dicyclohexylcarbodiimide; etc. These may be used alone or in combination of two or more kinds.
[0167] Since the copolymer 3 contained in the copolymer varnish has solvent solubility, a high concentration varnish can be obtained. The copolymer varnish preferably contains 5 to 40 mass % of copolymer 3, more preferably 10 to 30 mass %. The viscosity of the copolymer varnish is preferably 0.1 to 100 Pa·s, more preferably 0.1 to 20 Pa·s. The viscosity of the copolymer varnish is a value measured at 25°C using an E-type viscometer. In addition, the copolymer varnish may contain various additives such as inorganic fillers, adhesion promoters, release agents, flame retardants, UV stabilizers, surfactants, leveling agents, defoamers, fluorescent brightening agents, crosslinking agents, polymerization initiators, and photosensitizers, as long as the additives do not impair the required properties of the polyimide film. The method for producing the varnish is not particularly limited, and any known method can be applied.
[0168] The heating temperature when the copolymer varnish is dried to obtain a copolymer film is preferably 50 to 150° C. The heating temperature when the copolymer 3 is imidized by heating can be selected from the range of preferably 200 to 500° C., more preferably 250 to 450° C., and further preferably 300 to 400° C. The heating time is usually 1 minute to 6 hours, preferably 5 minutes to 2 hours, and more preferably 15 minutes to 1 hour. Examples of the heating atmosphere include air gas, nitrogen gas, oxygen gas, hydrogen gas, and nitrogen / hydrogen mixed gas. In order to suppress coloration of the resulting polyimide resin, nitrogen gas having an oxygen concentration of 100 ppm or less and nitrogen / hydrogen mixed gas containing a hydrogen concentration of 0.5% or less are preferred. The imidization method is not limited to thermal imidization, and chemical imidization can also be applied.
[0169] [Adjusting the moisture content of polyimide film] The water content of the polyimide film in the present invention is 1,000 to 35,000 ppm by mass. The method of adjusting the water content of the polyimide film within this range is not particularly limited, and the polyimide film may be produced by incorporating water when applying polyimide varnish onto a glass substrate or a silicon substrate, but it is more preferable to absorb moisture after the polyimide film is produced. In addition, after the polyimide film is produced, a metal film or an oxide semiconductor film may be laminated on the film, and various electronic devices may be produced and then absorb moisture. To allow the polyimide film to absorb moisture, it is preferable to hold the film for a predetermined period of time in a temperature and humidity environment with a temperature of preferably 10 to 40°C, more preferably 15 to 35°C, and a humidity of 40 to 80% RH, more preferably 50 to 70% RH, and particularly preferably 55 to 65% RH. The holding time is affected by the temperature and humidity, but is preferably 20 hours or more, more preferably 40 hours or more, even more preferably 60 hours or more, and is usually within 170 hours. Here, RH indicates relative humidity.
[0170] (Metal film or oxide semiconductor film) The laminate of the present invention has a metal film or an oxide semiconductor film further laminated on a polyimide film. By laminating a metal film or an oxide semiconductor film on a polyimide film, a target electronic device (conductive film) such as a touch sensor or an OLED can be produced on the polyimide film. Preferable specific examples of the metal film include copper mesh and silver mesh. A preferred example of the oxide semiconductor film is at least one selected from the group consisting of indium tin oxide (ITO), amorphous silicon, indium gallium zinc oxide (IGZO) and low temperature polysilicon (LTPS). On the metal film or oxide semiconductor film, another metal film or oxide semiconductor film may be further stacked. From the viewpoint of forming an electronic device on the polyimide film, the thickness of the metal film or oxide semiconductor film is from 1 to 400 nm, preferably from 10 to 300 nm, and more preferably from 20 to 200 nm.
[0171] The method for laminating a metal film or an oxide semiconductor film on a polyimide film is not particularly limited, but is preferably a physical vapor deposition method or a chemical vapor deposition method. Examples of the physical vapor deposition method include a vacuum vapor deposition method, a sputtering method, and an ion plating method, and examples of the chemical vapor deposition method include a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, and a photochemical vapor deposition method.
[0172] A conductive film can be obtained by peeling and removing the glass substrate or the silicon substrate from a laminate having a metal film or an oxide semiconductor film stacked thereon. That is, the method for producing a conductive film of the present invention includes a step of peeling and removing the glass substrate or the silicon substrate from the above-mentioned laminate. After laminating a metal film or an oxide semiconductor film on a polyimide film to produce a conductive film, the glass substrate or silicon substrate may be peeled off immediately to obtain the conductive film, or the conductive film may be obtained by storing the conductive film in a laminated state and, if necessary, peeling off the glass substrate or silicon substrate. Storing the conductive film in a laminated state is preferable because it improves the handling properties of the conductive film during transportation.
[0173] The method for peeling and removing the glass substrate or silicon substrate from the laminate is not particularly limited, but since the laminate of the present invention allows the polyimide film to be easily and stably peeled off from the glass substrate or silicon substrate, the laminate can be mechanically peeled off without laser irradiation. EXAMPLES
[0174] The present invention will be specifically described below with reference to examples, although the present invention is not limited to these examples in any way.
[0175] In the examples and comparative examples, the physical properties were measured by the methods shown below. (1) Film thickness The film thickness was measured using a laser microscope (manufactured by Keyence Corporation).
[0176] (2) Glass transition temperature (Tg) Using a thermomechanical analyzer "TMA / SS6100" (Hitachi High-Tech Science Corporation), the specimen was heated to a temperature sufficient to remove the residual stress in tensile mode under the conditions of a sample size of 2 mm x 20 mm, a load of 0.1 N, and a heating rate of 10°C / min, and then cooled to room temperature. The specimen elongation was then measured under the same conditions as in the treatment for removing the residual stress, and the point at which an inflection point in the elongation was observed was determined as the glass transition temperature.
[0177] (3) Total light transmittance, yellow index (YI) The total light transmittance and YI were measured in accordance with JIS K7105:1981 using a color / turbidity simultaneous measuring instrument "COH400" (manufactured by Nippon Denshoku Industries Co., Ltd.).
[0178] (4) Thickness phase difference (Rth) The thickness retardation (Rth) was measured using an ellipsometer "M-220" (manufactured by JASCO Corporation). The thickness retardation was measured at a measurement wavelength of 590 nm. Rth is expressed by the following formula, where the maximum in-plane refractive index of the polyimide film is nx, the minimum is ny, the refractive index in the thickness direction is nz, and the thickness of the film is d. Rth = [{(nx + ny) / 2}-nz] × d
[0179] (5) Moisture content of polyimide film The film was measured by the Karl Fischer method at 260℃ for 30 minutes using a trace moisture analyzer "CA-200" (manufactured by Mitsubishi Chemical Analytech Co., Ltd., a moisture meter using the Karl Fischer method) and a moisture vaporizer "VA-236S" (manufactured by Mitsubishi Chemical Analytech Co., Ltd., with a sample changer) as measuring equipment.
[0180] (6) Peel strength A 90° peel test was carried out based on JIS K6854-1 to measure the peel strength between the polyimide film and the glass interface. The peel strength was measured five times, and the average value was taken as the peel strength.
[0181] The tetracarboxylic acid components, diamine components, other components, and their abbreviations used in the production examples are as follows: <Tetracarboxylic acid component> HPMDA: 1,2,4,5-cyclohexanetetracarboxylic dianhydride (manufactured by Mitsubishi Gas Chemical Company, Inc.; compounds represented by formulas (a-11) and (a-21)) ODPA: 4,4'-oxydiphthalic anhydride (manufactured by Manac Corporation; compounds represented by formulas (a-12) and (a-22)) CpODA: norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride (manufactured by JX Nippon Oil & Energy Corporation; compound represented by formula (a-31-1) s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride (manufactured by Mitsubishi Chemical Corporation, compound represented by formula (a-32-1s)) <Diamine component> 3,3'-DDS: 3,3'-diaminodiphenyl sulfone (manufactured by Seika Corporation; compounds represented by formulas (b-11) and (b-21)) BAPS: bis[4-(4-aminophenoxy)phenyl]sulfone (manufactured by Seika Corporation; compound represented by formula (b-12)) HFBAPP: 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane (manufactured by Seika Corporation; compound represented by formula (b-22-3)) 6FODA: 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether (manufactured by ChinaTech (Tianjin) Chemical Co., Ltd., a compound represented by formula (b-31)) X-22-1660B-3: silicone oil modified with amino at both ends (manufactured by Shin-Etsu Chemical Co., Ltd., a compound represented by formula (b-32) (functional group equivalent: 2200 g / mol or 2170 g / mol) <Other> GBL: γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) TEA: Triethylamine (Kanto Chemical Co., Ltd.) NMP: N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation)
[0182] Manufacturing Example 1 Into a 300 mL five-neck round-bottom flask equipped with a stainless steel half-moon shaped stirring blade, a nitrogen inlet tube, a Dean-Stark equipped with a cooling tube, a thermometer, and a glass end cap, 13.845 g (0.056 mol) of 3,3'-DDS, 24.115 g (0.056 mol) of BAPS, and 41.903 g of GBL were placed and stirred at 200 rpm under a nitrogen atmosphere at an internal temperature of 70°C to obtain a solution. To this solution, 22.499g (0.100 mol) of HPMDA, 3.459g (0.011 mol) of ODPA, and 12.804g of GBL were added all at once, and then 0.564g of TEA was added as an imidization catalyst, and the mixture was heated with a mantle heater, raising the temperature in the reaction system to 190°C over about 20 minutes. The components that were distilled off were collected, and the rotation speed was adjusted according to the increase in viscosity, while maintaining the temperature in the reaction system at 190°C and refluxing for about 5 hours. Thereafter, 175.981 g of GBL was added so that the solid content concentration was 20 mass %, and the temperature inside the reaction system was cooled to 100° C., and the mixture was further stirred for about 1 hour to be homogenized, thereby obtaining Polyimide Varnish 1. Next, the obtained polyimide varnish 1 was applied onto a glass plate by spin coating and held on a hot plate at 80°C for 20 minutes, and then heated in an air atmosphere in a hot air dryer at 260°C for 30 minutes to evaporate the solvent, thereby obtaining a film.
[0183] Manufacturing Example 2 23.530 g (0.094 mol) of 3,3'-DDS, 12.247 g (0.024 mol) of HFBAPP, and 62.820 g of GBL were placed in a 300 mL five-neck round-bottom flask equipped with a stainless steel half-moon shaped stirring blade, a nitrogen inlet tube, a Dean-Stark equipped with a cooling tube, a thermometer, and a glass end cap, and the mixture was stirred at 200 rpm under a nitrogen atmosphere at an internal temperature of 70°C to obtain a solution. To this solution, 21.158g (0.094 mol) of HPMDA, 7.313g (0.024 mol) of ODPA, and 15.705g of GBL were added all at once, and then 0.596g of TEA was added as an imidization catalyst, and the mixture was heated with a mantle heater, raising the temperature in the reaction system to 190°C over about 20 minutes. The components distilled off were collected, and the temperature in the reaction system was maintained at 190°C and refluxed for 5 hours while adjusting the rotation speed according to the increase in viscosity. Thereafter, 161.475 g of GBL was added so that the solid content concentration was 20 mass %, and the temperature inside the reaction system was cooled to 100° C., and the mixture was further stirred for about 1 hour to be homogenized, thereby obtaining polyimide varnish 2. Next, the obtained polyimide varnish 2 was applied onto a glass plate by spin coating and held on a hot plate at 80°C for 20 minutes, and then heated in an air atmosphere in a hot air dryer at 260°C for 30 minutes to evaporate the solvent, thereby obtaining a film.
[0184] Production Example 3 26.953 g (0.0802 mol) of 6FODA and 56,000 g of NMP were added to a 500 mL five-neck round-bottom flask equipped with a stainless steel half-moon stirring blade, a nitrogen inlet tube, a Dean-Stark condenser, a thermometer, and a glass end cap, and the mixture was stirred at 200 rpm under a nitrogen atmosphere at an internal temperature of 70°C to obtain a solution. To this solution, 19.231g (0.050 mol) of CpODA and 14.000g of NMP were added all at once, and then 0.253g of TEA was added as an imidization catalyst, and the mixture was heated with a mantle heater, and the temperature in the reaction system was raised to 190°C over about 20 minutes. The components distilled off were collected, and the temperature in the reaction system was maintained at 190°C while adjusting the rotation speed according to the increase in viscosity, and refluxed for 1 hour. Then, 85.806g of NMP was added, and the temperature in the reaction system was cooled to 50°C, to obtain a solution containing an oligomer having an imide repeating structural unit. To the obtained solution, 9.814g (0.033 mol) of s-BPDA and 7.527g of NMP were added all at once and stirred at 50°C for 5 hours. After that, 100.000g of NMP was added and homogenized, and then a mixture of 14.002g (0.003 mol) of X-22-1660B-3 dissolved in 16.667g of NMP was added and stirred for about 1 hour to obtain varnish 3 containing a copolymer (PI-b-PAA) with a solid content concentration of about 20% by mass. Here, the copolymer having an imide repeating structural unit and an amic acid repeating structural unit is referred to as "PI-b-PAA". Next, the obtained varnish 3 was applied onto a glass plate by spin coating, and kept on a hot plate at 80°C for 20 minutes, and then heated in an air atmosphere in a hot air dryer at 350°C for 30 minutes to evaporate the solvent, thereby obtaining a polyimide film.
[0185] The above measurements were carried out on the polyimide films obtained in Production Examples 1 to 3. The results are shown in Tables 1 and 2.
[0186] [Table 1]
[0187] [Table 2]
[0188] Examples 1-2 and Comparative Example 1 The polyimide varnish 1 obtained in Production Example 1 was applied by spin coating onto a glass plate, held at 80°C for 20 minutes on a hot plate, and then heated at 260°C for 30 minutes in a hot air dryer under an air atmosphere to evaporate the solvent, obtaining a two-layer laminate (glass / polyimide film). Furthermore, a 30 nm thick SiO2 film was formed on the polyimide film of the laminate by sputtering, and a 120 nm thick ITO film was formed thereon to obtain a four-layer laminate (glass / polyimide film / SiO2 film / ITO film). The obtained four-layer laminate was held under the conditions described in Table 3 to adjust the moisture content of the polyimide film in the four-layer laminate.
[0189] Examples 3 to 4 and Comparative Example 2 The polyimide varnish 2 obtained in Production Example 2 was applied by spin coating onto a glass plate, held at 80°C for 20 minutes on a hot plate, and then heated at 260°C for 30 minutes in a hot air dryer under an air atmosphere to evaporate the solvent, obtaining a two-layer laminate (glass / polyimide film). Furthermore, a 30 nm thick SiO2 film was formed on the polyimide film of the laminate by sputtering, and a 120 nm thick ITO film was formed thereon to obtain a four-layer laminate (glass / polyimide film / SiO2 film / ITO film). The obtained four-layer laminate was held under the conditions described in Table 3 to adjust the moisture content of the polyimide film in the four-layer laminate.
[0190] Examples 5 to 6 The varnish 3 obtained in Production Example 3 was applied by spin coating onto a glass plate, held at 80°C for 20 minutes on a hot plate, and then heated at 350°C for 30 minutes in a hot air dryer under an air atmosphere to evaporate the solvent, obtaining a two-layer laminate (glass / polyimide film). Furthermore, a 30 nm thick SiO2 film was formed on the polyimide film of the laminate by sputtering, and a 120 nm thick ITO film was formed thereon to obtain a four-layer laminate (glass / polyimide film / SiO2 film / ITO film). The obtained four-layer laminate was held under the conditions shown in Table 3 to adjust the moisture content of the polyimide film in the four-layer laminate.
[0191] The laminate obtained above was subjected to the above-mentioned peel test, and the results are shown in Table 3. For the laminate of Comparative Example 1, the film could not be peeled off from the glass, and the peel strength could not be measured. For the laminate of Comparative Example 2, the film broke when peeled off from the glass, and the peel strength could not be measured.
[0192] [Table 3]
[0193] The results in Table 3 show that the laminate of the present invention, in which the moisture content of the polyimide film is adjusted to fall within a predetermined range, has a relatively low peel strength and allows the polyimide film to be easily and stably peeled off from the glass substrate or silicon substrate. It is apparent from the results in Tables 1 and 2 that all of the polyimide films of Production Examples 1 to 3 are excellent in colorless transparency and optical isotropy.
Claims
1. A laminate comprising a polyimide film adhered to a glass substrate, and a metal film or an oxide semiconductor film further laminated on the polyimide film, wherein the metal film or the oxide semiconductor film has a thickness of 1 to 400 nm, the water content of the polyimide film is 1,000 to 35,000 ppm by mass, and the peel strength of the polyimide film from the glass substrate is 20 gf / cm or less.
2. 2. The laminate according to claim 1, wherein the polyimide film has a film thickness of 3 to 20 μm.
3. 3. The laminate according to claim 1, wherein the oxide semiconductor film is at least one selected from the group consisting of indium tin oxide, amorphous silicon, indium gallium zinc oxide, and low-temperature polysilicon.
4. A conductive film obtained by peeling and removing the glass substrate from the laminate according to any one of claims 1 to 3.
5. laminating a polyimide film on a glass substrate; adjusting the moisture content of the polyimide film to 1,000 to 35,000 ppm by mass; A step of laminating a metal film or an oxide semiconductor film having a thickness of 1 to 400 nm on a polyimide film; and A process to peel and remove the glass substrate Including, The method for producing a conductive film, wherein the polyimide film has a peel strength from a glass substrate of 20 gf / cm or less.
6. The method for producing a conductive film according to claim 5, wherein the step of adjusting the moisture content of the polyimide film is a step of maintaining the polyimide film in a temperature and humidity environment of 10 to 40° C. and 40 to 80% RH for 20 hours or more.
7. 7. The method for producing a conductive film according to claim 5, wherein the step of laminating a metal film or an oxide semiconductor film on the polyimide film is performed by a physical vapor deposition method or a chemical vapor deposition method.
Citation Information
Patent Citations
Aromatic polyimide film having low heat shrinkage stress and high adhesion and method for producing the same
JP2003147099A
Method for manufacturing circuit board
JP2004319869A
Active matrix displays and other electronic devices with plastic substrates
JP2007512568A
Substrate structure applied in flexible electronic device and fabrication method thereof
JP2010067957A
Resin molded product and method for producing the same
JP2010222566A